Resin composition, and multilayer structure and packaging material using same

The resin composition with ethylene-cyclic olefin copolymer and transition metal catalyst addresses odor and decomposition issues in packaging, maintaining effective oxygen absorption and barrier properties for pet food packaging.

JP7604371B2Active Publication Date: 2024-12-23KURARAY CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021528280
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-09
Filing Date
2020-06-26
Publication Date
2024-12-23
Estimated Expiration
2040-06-26

AI Technical Summary

Technical Problem

Existing oxygen-absorbing resin compositions used in packaging materials generate unpleasant odors and volatile decomposition products due to side reactions, particularly affecting pet food packaging, which can deter consumers and reduce product credibility.

Method used

A resin composition containing an ethylene-cyclic olefin copolymer with specific ratios of norbornene units and a transition metal catalyst, along with additional components like EVOH and acetic acid adsorbing materials, is developed to minimize odor generation and volatile decomposition products during oxygen absorption.

Benefits of technology

The resin composition effectively absorbs oxygen while significantly reducing the generation of unpleasant odors and volatile decomposition products, ensuring high oxygen barrier properties even after retort treatment, suitable for packaging sensitive products like pet food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604371000014
    Figure 0007604371000014
  • Figure 0007604371000001
    Figure 0007604371000001
  • Figure 0007604371000002
    Figure 0007604371000002
Patent Text Reader

Abstract

This resin composition contains: an ethylene–cyclic olefin copolymer (A) that includes a repeating unit that is represented by formula (I) and has an ethylene unit and a norbornene unit that has a substituent R1; and a transition metal catalyst (B). In the formula, R1 represents an ethylene group or an ethylene group that is substituted with a C1–3 aliphatic hydrocarbon group, and l and n respectively represent the content ratios of the ethylene unit and the norbornene unit that has the substituent R1, the ratio (l / n) of l and n being 4–2,000.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and a multilayer structure and a packaging material using the same, and more particularly to a resin composition having excellent oxygen absorbing properties, and a multilayer structure and a packaging material using the same. [Background technology]

[0002] Gas barrier resins, such as ethylene-vinyl alcohol copolymers (hereinafter sometimes abbreviated as EVOH), are materials with excellent oxygen barrier properties. Since such resins can be melt molded, they are preferably used as multi-layer packaging materials by laminating them with layers of thermoplastic resins (polyolefins, polyesters, etc.) that are excellent in moisture resistance and mechanical properties. However, the gas permeability of these gas barrier resins is not completely zero, and they allow a non-negligible amount of gas to pass through. In order to reduce the permeation of such gases, particularly the permeation of oxygen that has a significant effect on the quality of the contents of the package, especially food, and to absorb and remove the oxygen already present in the package at the time of packaging the contents, it is known to use a resin composition containing a component having oxygen absorbing properties in the packaging material.

[0003] For example, Patent Document 1 discloses the use of a resin composition containing ethylene-propylene-diene rubber containing 5-ethylidene-2-norbornene and manganese stearate as an oxygen-absorbing resin layer constituting a packaging material. Patent Document 2 discloses an oxygen-absorbing resin containing a polyolefin resin polymerized using a single-site catalyst such as a metallocene catalyst. Patent Document 3 discloses an oxygen-absorbing resin composition containing a polyolefin resin and an oxidation catalyst not supported on a carrier.

[0004] In addition, while EVOH exhibits excellent oxygen barrier properties under low humidity conditions, when a container having a multilayer structure containing EVOH is subjected to a high-temperature, high-pressure hot water treatment such as retort treatment, it may cause a retort shock phenomenon in which the oxygen barrier properties are significantly reduced, and the quality of the contents of the container may be reduced. Patent Document 4 discloses a resin composition consisting of EVOH, polyoctenylene, and a transition metal catalyst as a resin composition that exhibits high oxygen barrier properties even after retort treatment. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-234718 A [Patent Document 2] JP 2005-320513 A [Patent Document 3] JP 2007-076365 A [Patent Document 4] JP 2008-201432 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, although all of the oxygen-absorbing resin compositions described in Patent Documents 1 to 3 have a reasonable oxygen absorbing ability, a part of the structure of the resin, which is the main component that exhibits the oxygen absorbing ability, may be decomposed by reaction with oxygen molecules, and various volatile decomposition products that cause unpleasant odors (for example, fatty acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, and caproic acid, and aldehydes such as acetaldehyde, propanal, butanal, valeraldehyde, and hexanal) may be generated. The resin composition described in Patent Document 4 has good oxygen barrier properties after retort treatment, but may cause the resin to be colored after retort treatment, or may emit an unpleasant odor due to the generation of volatile decomposition products associated with side reactions of the oxidation reaction. In particular, in applications such as food (pet food) for dogs and cats, which are more sensitive to odors than humans, the unpleasant odor caused by such volatile decomposition products is avoided by food producers and consumers who purchase products packaged with packaging materials, which may lead to a decrease in the reliability of the products and a decrease in purchasing motivation.

[0007] The present invention has an object to solve the above problems, and has an object to provide a resin composition that has excellent oxygen absorption properties, generates a low odor intensity after absorbing oxygen, and produces a small number of volatile decomposition products after absorbing oxygen, and a multilayer structure and packaging material using the same. [Means for solving the problem]

[0008] The present invention includes the following inventions. [1] An ethylene unit represented by the following formula (I) and a substituent R 1 A resin composition comprising an ethylene-cyclic olefin copolymer (A) containing a repeating unit with a norbornene unit having the formula: and a transition metal catalyst (B), [ka] In the formula, R 1 represents an ethylene group or an ethylene group substituted with an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and l and n represent the ethylene unit and the substituent R 1wherein the ratio of l to n (l / n) is 4 or more and 2,000 or less. [2] The ethylene-cyclic olefin copolymer (A) comprises an ethylene unit and a substituent R 2 and an ethylene unit having a substituent R 1 and a norbornene unit having the formula [ka] (In the formula, R 1 represents an ethylene group or an ethylene group substituted with an aliphatic hydrocarbon group having 1 to 3 carbon atoms, R 2 represents an aliphatic hydrocarbon group having 1 to 8 carbon atoms; l, m, and n each represent the ethylene unit, the substituent R 2 and the substituent R 1 (represents the content ratio of norbornene units having the formula The resin composition according to [1], wherein l, m and n satisfy the relationship of the following formula (III): 0.0005≦n / (l+m+n)≦0.2 (III) [3] R in formula (II) 2 is at least one group selected from the group consisting of a linear, branched or cyclic alkyl group having 1 to 8 carbon atoms; a linear, branched or cyclic alkenyl group having 2 to 8 carbon atoms; and a linear, branched or cyclic alkynyl group having 2 to 8 carbon atoms. [4] R in the above formula (I) or (II) 1 is an ethylene group substituted with at least one aliphatic hydrocarbon group selected from the group consisting of a linear, branched or cyclic alkyl group having 1 to 3 carbon atoms; a linear, branched or cyclic alkenyl group having 2 to 3 carbon atoms; an alkynyl group having 2 to 3 carbon atoms; and a linear or branched alkylidene group having 2 to 3 carbon atoms. [5] R in the above formula (I) or (II) 1 The resin composition according to any one of [1] to [4], wherein [6] The resin composition according to any one of [1] to [5], wherein the main chain of the ethylene-cyclic olefin copolymer (A) is composed of only single bonds. [7] The ethylene-cyclic olefin copolymer (A) is a copolymer having a branched chain composed of at least one alkyl group selected from the group consisting of an n-butyl group, an n-pentyl group, and an n-hexyl group, and the ethylene-cyclic olefin copolymer (A) 13 The resin composition according to any one of [1] to [6], wherein the total number of the alkyl groups constituting the branched chains per 1,000 carbon atoms is 0.001 to 50, as determined by C NMR. [8] The resin composition according to any one of [1] to [7], which has an oxygen absorption rate of 0.1 to 300 mL / g for 7 days under conditions of 60°C and 10% RH. [9] The resin composition according to any one of [1] to [8], wherein the content of the transition metal catalyst (B) is 20 to 10,000 ppm in terms of metal atoms.

[10] The content X (ppm) of the transition metal catalyst (B) in terms of metal atoms and the substituent R in all monomer units constituting the ethylene-cyclic olefin copolymer (A) 1 and a content ratio Y (mol %) of norbornene units having the formula (IV) below are satisfied. 11≦X / Y≦10000 (IV)

[11] The content X (ppm) of the transition metal catalyst (B) in terms of metal atoms and the substituent R in all monomer units constituting the ethylene-cyclic olefin copolymer (A) 1 and the content ratio Y (mol %) of norbornene units having the substituent R 2 and a content ratio Z (mol %) of the ethylene unit having the formula (V) below are satisfied: 0.1≦X / (Y+Z)≦150 (V)

[12] The resin composition according to any one of [1] to

[11] , wherein the content of the ethylene-cyclic olefin copolymer (A) is 25.0 to 99.9 mass % based on the total amount of the resin composition.

[13] The resin composition according to any one of [1] to

[11] , further comprising an ethylene-vinyl alcohol copolymer (C).

[14] The resin composition according to

[13] , wherein the content of the ethylene-cyclic olefin copolymer (A) is 0.5 to 50 mass % based on the total amount of the resin composition.

[15] The resin composition according to

[13] or

[14] , wherein the content of the ethylene-vinyl alcohol copolymer (C) is 50 to 99.5 mass % based on the total amount of the resin composition.

[16] The resin composition according to any one of

[13] to

[15] , further comprising an alkaline earth metal salt, the content of the alkaline earth metal salt being 1 to 1000 ppm in terms of the metal element.

[17] The resin composition according to any one of [1] to

[16] , further comprising an aluminum compound (D) in an amount of 0.1 to 10,000 ppm calculated as aluminum metal atom.

[18] The resin composition according to any one of [1] to

[17] , further comprising an acetic acid adsorbing material (E).

[19] The resin composition according to

[18] , wherein the acetic acid adsorbing material (E) contains zeolite, and the content of the zeolite is 0.1 to 20 mass % based on the total amount of the resin composition.

[20] The resin composition according to

[19] , wherein the zeolite has an average pore diameter of 0.3 to 1 nm.

[21] The resin composition according to any one of [1] to

[20] , further comprising an antioxidant (F), the content of the antioxidant being 0.001 to 1 mass % based on the total amount of the resin composition.

[22] The resin composition according to any one of [1] to

[21] , wherein the ethylene-cyclic olefin copolymer (A) has an MFR value of 2 g / 10 min or less at 190° C. under a load of 2160 g, and further contains a viscosity modifier having an MFR of 10 g / 10 min or more at 190° C. under a load of 2160 g, and the content of the viscosity modifier is 1 to 30 mass % based on the total amount of the resin composition.

[23] A multilayer structure having at least one oxygen-absorbing layer comprising the resin composition according to any one of the above [1] to

[22] .

[24] The multilayer structure according to

[23] , having at least one gas barrier resin layer.

[25] A packaging material comprising the multilayer structure described in

[24] above.

[26] A packaging material according to

[25] that contains a content and surrounds the content, A packaged product, wherein the oxygen absorbing layer in the packaging material is disposed between the gas barrier resin layer in the packaging material and the contents.

[27] The packaged product described in

[26] , wherein the contents are food. Effect of the Invention

[0009] According to the present invention, the oxygen absorbency is excellent, and the generation of volatile decomposition products during oxygen absorption can be prevented, thereby suppressing the generation of unpleasant odors associated therewith. As a result, it is possible to provide containers and packaging materials, such as multilayer films and multilayer containers, suitable for storing products such as food that are susceptible to deterioration by oxygen. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 shows GC-MS graphs to confirm the presence or absence of volatile decomposition products that are generated when oxygen is absorbed into the oxygen-absorbing films produced in Example I-1 and Comparative Example I-3. The graph at the bottom of the figure is for the oxygen-absorbing film produced in Example I-1, and the graph at the top of the figure is for the oxygen-absorbing film produced in Comparative Example I-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] (1) Resin composition The resin composition of the present invention contains an ethylene-cyclic olefin copolymer (A) and a transition metal catalyst (B).

[0012] (Ethylene-cyclic olefin copolymer (A)) The ethylene-cyclic olefin copolymer (A) may be, for example, an ethylene unit and a substituent R 1and norbornene units having the formula (I):

[0013] [ka]

[0014] In formula (I), R 1 R represents an ethylene group or an ethylene group in which at least one hydrogen atom constituting the ethylene group has been substituted with an aliphatic hydrocarbon group having 1 to 3 carbon atoms. 1 More specific examples of the aliphatic hydrocarbon group having 1 to 3 carbon atoms included in the above formula include linear, branched or cyclic alkyl groups having 1 to 3 carbon atoms (i.e., including linear alkyl groups having 1 to 3 carbon atoms, branched alkyl groups having 3 carbon atoms, and cyclic alkyl groups having 3 carbon atoms); linear, branched or cyclic alkenyl groups having 2 to 3 carbon atoms (i.e., including linear alkenyl groups having 1 to 3 carbon atoms, branched alkenyl groups having 3 carbon atoms, and cyclic alkenyl groups having 3 carbon atoms); alkynyl groups having 2 to 3 carbon atoms (i.e., including linear alkynyl groups having 2 to 3 carbon atoms); and linear or branched alkylidene groups having 2 to 3 carbon atoms (i.e., including linear alkylidene groups having 2 to 3 carbon atoms and branched alkylidene groups having 3 carbon atoms).

[0015] R 1 Examples of the linear, branched or cyclic alkyl group having 1 to 3 carbon atoms that can constitute R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group and a cyclopropyl group. 1 Examples of the linear, branched or cyclic alkenyl group having 2 to 3 carbon atoms that can constitute R include a vinyl group, a 1-propenyl group, a 2-propenyl group and a cyclopropenyl group. 1 Examples of the linear or branched alkynyl group having 2 to 3 carbon atoms that can constitute R include an ethynyl group, a 1-propynyl group, and a 2-propynyl group (propargyl group). 1Examples of the linear or branched alkylidene group having 2 to 3 carbon atoms that can constitute the formula (I) include an ethylidene group, a 1-propylidene group, and a 2-propylidene group. 1 is preferably an ethylideneethylene group.

[0016] In formula (I), l and n represent an ethylene unit and a substituent R 1 The ratio of l to n (l / n) is 4 or more and 2000 or less, preferably 5 or more and 500 or less, and more preferably 10 or more and 100 or less. In formula (I), if the ratio of l to n is less than 4, the glass transition temperature of the resin becomes high and a sufficient oxygen absorption rate may not be obtained. If the ratio of l to n exceeds 2000, the proportion of norbornene units constituting the copolymer is too small, and the obtained copolymer may not exhibit sufficient oxygen absorption properties.

[0017] In addition, the substituent R in the ethylene-cyclic olefin copolymer (A) 1 The norbornene unit having the substituent R 1 It may be composed of one type of monomer unit, or may be composed of two or more different types of monomer units.

[0018] The ethylene-cyclic olefin copolymer (A) is composed of ethylene units and substituents R 2 and an ethylene unit having a substituent R 1 It is preferable that the copolymer is a random copolymer represented by formula (II) containing a repeating unit having a norbornene unit having the formula:

[0019] [ka]

[0020] In formula (II), R 1 is the same as defined in formula (I) above. In formula (II), R 1 R is preferably an ethylideneethylene group. 2is an aliphatic hydrocarbon group having 1 to 8 carbon atoms, preferably a linear, branched or cyclic alkyl group having 1 to 8 carbon atoms; a linear, branched or cyclic alkenyl group having 2 to 8 carbon atoms; or a linear, branched or cyclic alkynyl group having 2 to 8 carbon atoms; and more preferably a linear, branched or cyclic alkyl group having 1 to 3 carbon atoms; a linear, branched or cyclic alkenyl group having 2 to 3 carbon atoms; or an alkynyl group having 2 to 3 carbon atoms. Here, the term "linear, branched or cyclic alkyl group having 1 to 8 carbon atoms" as used in this specification includes linear alkyl groups having 1 to 8 carbon atoms, branched alkyl groups having 3 to 8 carbon atoms, and cyclic alkyl groups having 3 to 8 carbon atoms. The term "straight-chain, branched-chain or cyclic alkenyl group having 2 to 8 carbon atoms" as used herein includes straight-chain alkenyl groups having 2 to 8 carbon atoms, branched-chain alkenyl groups having 3 to 8 carbon atoms, and cyclic alkenyl groups having 3 to 8 carbon atoms. The term "straight-chain, branched-chain or cyclic alkynyl groups having 2 to 8 carbon atoms" as used herein includes straight-chain alkynyl groups having 2 to 8 carbon atoms, branched-chain alkynyl groups having 3 to 8 carbon atoms, and cyclic alkynyl groups having 3 to 8 carbon atoms.

[0021] R 2 Examples of the linear, branched or cyclic alkyl group having 1 to 8 carbon atoms that can constitute R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a 3-pentyl group, an n-hexyl group, an n-heptyl group, a 4-heptyl group, an n-octyl group, a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group. 2Examples of the linear, branched or cyclic alkenyl group having 2 to 8 carbon atoms that can constitute the above group include a vinyl group, a 1-propenyl group, a 2-propenyl group, an isopropenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, an isobutenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, a 4-pentenyl group, an isopentenyl group, a cyclopentenyl group, a 1-hexenyl group, a 2 R includes, for example, a 1-hexenyl group, a 3-hexenyl group, a 4-hexenyl group, a 5-hexenyl group, a cyclohexenyl group, a 1-heptenyl group, a 2-heptenyl group, a 3-heptenyl group, a 4-heptenyl group, a 5-heptenyl group, a 6-heptenyl group, a 1-octenyl group, a 2-octenyl group, a 3-octenyl group, a 4-octenyl group, a 5-octenyl group, a 6-octenyl group, and a 7-octenyl group. 2 Examples of the linear, branched or cyclic alkynyl group having 2 to 8 carbon atoms that can constitute the formula (II) include an ethynyl group, a 1-propynyl group, a 2-propynyl group, a 1-butynyl group, a 2-butynyl group, a 3-butynyl group, a 1-pentynyl group, a 2-pentynyl group, a 3-pentynyl group, a 4-pentynyl group, a 1-hexynyl group, a 2-hexynyl group, a 3-hexynyl group, a 4-hexynyl group, a 5-hexynyl group, a 1-heptynyl group, a 2-heptynyl group, a 3-heptynyl group, a 4-heptynyl group, a 5-heptynyl group, a 6-heptynyl group, a 1-octynyl group, a 2-octynyl group, a 3-octynyl group, a 4-octynyl group, a 5-octynyl group, a 6-octynyl group, a 7-octynyl group, and the like. 2 is preferably a methyl group or an ethyl group.

[0022] In formula (II), l, m and n are each an ethylene unit, a substituent R 2 and an ethylene unit having a substituent R 1 The ratio (n / (l+m+n)) of n to the sum (l+m+n) of l, m, and n satisfies the following relational formula (III): 0.0005≦n / (l+m+n)≦0.2 (III) It is preferable that the ratio (n / (l+m+n)) satisfies the above. Furthermore, the ratio (n / (l+m+n)) is more preferably 0.008 or more and 0.08 or less, and even more preferably 0.01 or more and 0.05 or less. In formula (II), if the ratio (n / (l+m+n)) is less than 0.0005, sufficient oxygen absorption may not be achieved. If the ratio (n / (l+m+n)) exceeds 0.2, the glass transition temperature of the resin becomes high, and a sufficient oxygen absorption rate may not be achieved.

[0023] In addition, the substituent R in the ethylene-cyclic olefin copolymer (A) 1 and a norbornene unit having a substituent R 2 The ethylene unit having the substituent R 1 and the substituent R 2 may each be composed of one type of monomer unit, or may each be composed of two or more different types of monomer units.

[0024] In the present invention, it is preferable that the ethylene-cyclic olefin copolymer (A) represented by the above formula (I) or (II) has a main chain in the structure represented by formula (I) or (II) composed of only single bonds, i.e., the main chain does not contain unsaturated bonds such as double bonds.

[0025] In general, when the main chain constituting the structure of the repeating unit contains an unsaturated bond (double bond or triple bond), the reactivity of the unsaturated bond contained in the ring portion not constituting the main chain in the structure is higher than that of the unsaturated bond constituting the main chain, so that an increase in the amount of oxygen absorbed by the ring portion at room temperature can be expected. Therefore, when the ring portion contains an unsaturated bond, the unsaturation of the ring portion not constituting the main chain preferentially absorbs oxygen before the unsaturated bond of the main chain absorbs oxygen, and the opportunity for oxygen absorption by the unsaturated bond of the main chain can be delayed as much as possible. As a result, the main chain is less likely to break, and the new generation of odorous components due to the breakage is suppressed. However, even in such a case, if the main chain contains an unsaturated bond, the possibility of the main chain breaking is inherent, even if it is only a small amount.

[0026] In contrast, when the main chain of the ethylene-cyclic olefin copolymer (A) represented by the above formula (I) or (II) is composed of only single bonds, the reaction for absorbing oxygen mainly occurs through the unsaturated bonds contained in the ring portion, and the possibility of main chain scission can be further reduced.

[0027] As a result, in the present invention, the possibility of generation of odorous components accompanying main chain scission, particularly low molecular weight odorous components due to main chain scission (for example, volatile decomposition products such as fatty acids such as propionic acid, butyric acid, valeric acid, and caproic acid, and aldehydes such as acetaldehyde, pentanal, butanal, and hexanal) is further reduced.

[0028] The weight average molecular weight (Mw) of the ethylene-cyclic olefin copolymer (A) in terms of standard polystyrene is preferably 5,000 to 500,000, more preferably 10,000 to 300,000, and even more preferably 20,000 to 200,000. If the weight average molecular weight (Mw) of the ethylene-cyclic olefin copolymer (A) is less than 5,000, the moldability, handling property, and mechanical properties such as strength and elongation of the molded product of the resin composition may be reduced. If the weight average molecular weight (Mw) of the ethylene-cyclic olefin copolymer (A) exceeds 500,000, the ethylene-cyclic olefin copolymer (A) becomes highly viscous and the moldability deteriorates, and when used in combination with other resins such as gas barrier resins, the dispersibility of the ethylene-cyclic olefin copolymer (A) itself decreases, thereby reducing the oxygen absorption function, and the performance of the gas barrier resin (for example, gas barrier property) may not be fully exhibited.

[0029] The ethylene-cyclic olefin copolymer (A) is, as a whole copolymer, i.e., R 1 or R in the above formula (II) 2It is preferable that the ethylene-cyclic olefin copolymer (A) has a branched chain having 4 or more carbon atoms (hereinafter referred to as other branched chain) in a certain range other than the above. Examples of such other branched chains include alkyl groups such as n-butyl group, n-pentyl group, and n-hexyl group. Furthermore, in the ethylene-cyclic olefin copolymer (A), for example, 13 The total number of alkyl groups constituting the other branched chains per 1000 carbon atoms obtained by C NMR is preferably 0.001 to 50, more preferably 0.002 to 5, and even more preferably 0.003 to 3. When the total number of alkyl groups is within such a range, the crystallinity is appropriately reduced and moldability is improved, and the generation of odors originating from fatty acids and aldehydes having 4 or more carbon atoms generated by side reactions accompanying the oxidation reaction can be suppressed.

[0030] The ethylene-cyclic olefin copolymer (A) used in the present invention can be synthesized by a known method such as a coordination polymerization method, a radical polymerization method, etc. Specific examples of the coordination polymerization method include the method described in the non-patent literature Polymers, 2017, 9, 353.

[0031] The polymerization catalyst used in the synthesis of the ethylene-cyclic olefin copolymer (A) by the coordination polymerization method can be a known catalyst for olefin coordination polymerization. Examples of the catalyst for olefin coordination polymerization include multi-site catalysts such as Ziegler-Natta catalysts and Phillips catalysts, and single-site catalysts such as metallocene catalysts.

[0032] Among them, the use of a single-site catalyst allows the synthesis of an ethylene-cyclic olefin copolymer (A) with a low branching amount. In addition, the use of a Ziegler-Natta catalyst consisting of a combination of a soluble vanadium compound such as vanadium oxyethoxide dichloride and an equal blend of ethylaluminum dichloride and diethylaluminum chloride allows the synthesis of an ethylene-cyclic olefin copolymer (A) with a narrow molecular weight distribution while providing a constant branching amount. The branching amount can be adjusted to a preferred range by selecting a catalyst as necessary. In addition, the branching amount in the resin composition can be adjusted by mixing multiple types of ethylene-cyclic olefin copolymers (A) that have been polymerized separately.

[0033] In addition, when an aluminum compound is used as a catalyst or co-catalyst, the oxygen absorption of the resulting mixture (resin composition) of the ethylene-cyclic olefin copolymer (A) with the transition metal catalyst (B) and EVOH (C) described below can be further improved.

[0034] When an aluminum compound is used as a catalyst or co-catalyst in synthesizing ethylene-cyclic olefin copolymer (A), the aluminum compound may react with a surrounding polymer and be incorporated into the polymer. For example, when quantifying the content of the aluminum compound thus incorporated from a resin composition of ethylene-cyclic olefin copolymer (A) with a transition metal catalyst (B) and EVOH (C) described below, the ethylene-cyclic olefin copolymer (A) is extracted from the resin composition in a non-polar solvent such as cyclohexane or toluene, and then concentrated or reprecipitated in a polar solvent such as acetone, and the isolated ethylene-cyclic olefin copolymer (A) is subjected to wet decomposition in a strong acid by microwave heating, and the content can be quantified using an analytical means such as ICP-MS.

[0035] The melt flow rate (MFR) of the ethylene-cyclic olefin copolymer (A) is preferably in the range of 0.1 to 10, i.e., the ratio MFR(A) / MFR(C) of the MFR of the EVOH (C). When the ratio MFR(A) / MFR(C) is in this range, the dispersibility of both during melt kneading is good, the amount of scum generated in the die during melt kneading is reduced, the productivity is improved, and the amount of lumps in the molded product is reduced, resulting in a good appearance. The MFR referred to here is the value measured when the ethylene-cyclic olefin copolymer (A) is measured at 190°C under a load of 2160g.

[0036] Some ethylene-cyclic olefin copolymers (A) are commercially available, for example, EPDM (ethylene propylene diene rubber) elastomers composed of ethylene, propylene, and ethylidene norbornene monomers, and cycloolefin copolymers composed of ethylene and norbornene monomers. When using commercially available products, additives such as lubricants and antioxidants may be included, but the additives may be removed by reprecipitation or stirring and washing in an organic solvent as necessary. Specifically, the additives can be removed by adding a cyclohexane solvent to an EPDM elastomer or cycloolefin copolymer in an oil bath at 90°C to dissolve it, and then reprecipitation in acetone, which is a poor solvent. More simply, the additives can be removed by refluxing and stirring pellets of EPDM elastomer or the like in acetone. In the present invention, it is preferable that commercially available ethylene-cyclic olefin copolymers (A) also contain aluminum compounds. Among them, it is more preferable that the aluminum compounds remain even after the above-mentioned additive removal treatment is performed. Examples of such commercially available ethylene-cyclic olefin copolymer (A) products include "Mitsui EPT K-9720" (manufactured by Mitsui Chemicals, Inc., MFR (190°C, 2160g load) = 2g / 10min), "NORDEL IP4820P" (manufactured by Dow Chemical, MFR = 1g / 10min), "NORDEL IP4770P" (manufactured by Dow Chemical, MFR = 0.07g / 10min), "NORDEL IP4725P" (manufactured by Dow Chemical, MFR = 0.7g / 10min), and "TOPAS E-140" (manufactured by Polyplastics Co., Ltd., MFR = 3g / 10min).

[0037] In the resin composition of the present invention, the content of the ethylene-cyclic olefin copolymer (A) is, for example, 0.01 to 99.99 mass % based on the total amount of the resin composition.

[0038] Here, the content of the ethylene-cyclic olefin copolymer (A) is preferably 25.0 to 99.9 mass%, more preferably 30 to 99.8 mass%, and even more preferably 40 to 99.6 mass% when the resin composition of the present invention does not contain EVOH (C) described below. When the resin composition of the present invention does not contain EVOH (C), if the content of the ethylene-cyclic olefin copolymer (A) in the resin composition is less than 25.0 mass%, the oxygen absorption of the resulting resin composition may be insufficient. If the content of the ethylene-cyclic olefin copolymer (A) exceeds 99.99 mass%, the amount of transition metal catalyst or the like added for oxidation becomes small, and sufficient oxygen absorption may not be exhibited.

[0039] Alternatively, the content of the ethylene-cyclic olefin copolymer (A) is preferably 0.01 to 99.0% by mass, more preferably 0.5 to 50% by mass, and even more preferably 1.0 to 20% by mass when the resin composition of the present invention contains EVOH (C) described below. When the resin composition of the present invention contains EVOH (C), if the content of the ethylene-cyclic olefin copolymer (A) in the resin composition is less than 0.01% by mass, the oxygen absorption of the resulting resin composition may be insufficient. If the content of the ethylene-cyclic olefin copolymer (A) is more than 90% by mass, the content of EVOH (C) is relatively small, and sufficient gas barrier properties may not be exhibited.

[0040] (Transition metal catalyst (B)) The transition metal catalyst (B) is a compound that plays a role in promoting oxygen absorption by oxidation of the ethylene-cyclic olefin copolymer (A). The transition metal catalyst (B) is preferably in the form of an inorganic acid salt, an organic acid salt, or a complex salt of a transition metal. The transition metal atom constituting the transition metal catalyst (B) is selected from metal atoms belonging to Group VIII of the periodic table such as iron, cobalt, nickel, etc.; metal atoms belonging to Group I of the periodic table such as copper, silver, etc.; metal atoms belonging to Group IV of the periodic table such as tin, titanium, zirconium, etc.; metal atoms belonging to Group V of the periodic table such as vanadium, metal atoms belonging to Group VI of the periodic table such as chromium, metal atoms belonging to Group VII of the periodic table such as manganese, etc., and combinations thereof. The transition metal atom constituting the transition metal catalyst (B) is preferably manganese or cobalt, in view of its versatility and ability to efficiently oxidize the ethylene-cyclic olefin copolymer (A).

[0041] Examples of inorganic acid salts of the transition metal catalyst (B) include halides such as chlorides, sulfur oxyacid salts such as sulfates, nitrogen oxyacid salts such as nitrates, phosphorus oxyacid salts such as phosphates, silicates, etc., which contain the above transition metal atoms. Examples of organic acid salts of the transition metal catalyst (B) include acetates, propionates, isopropionates, butanoates, isobutanoates, pentanoates, isopentanoates, hexanoates, heptanoates, isoheptanoates, octanoates, 2-ethylhexanoates, nonanoates, 3,5,5-trimethylhexanoates, decanoates, neodecanoates, undecanoates, laurates, myristates, palmitates, margarates, stearates, arachidates, linderates, tuzanates, petroselinates, oleates, linoleates, linolenates, arachidonates, formates, oxalates, sulfamates, naphthenates, etc., which contain the above transition metal atoms. The complex salt of the transition metal catalyst (B) may be a complex of the above transition metal atom with a β-diketone or a β-keto acid ester. Specific examples of the β-diketone and the β-keto acid ester include acetylacetone, ethyl acetoacetate, 1,3-cyclohexadione, methylenebis-1,3-cyclohexadione, 2-benzyl-1,3-cyclohexadione, acetyltetralone, palmitoyltetralone, stearoyltetralone, benzoyltetralone, 2-acetylcyclohexanone, 2-benzoylcyclohexanone, 2-acetyl-1,3-cyclohexanedione, benzoyl-p-chlorobenzoylmethane, bis(4-methylphenyl)-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methylphenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methylphenyl, 2-methyl-phenyl-2-methyl- ... ethylbenzoyl)methane, bis(2-hydroxybenzoyl)methane, benzoylacetone, tribenzoylmethane, diacetylbenzoylmethane, stearoylbenzoylmethane, palmitoylbenzoylmethane, lauroylbenzoylmethane, dibenzoylmethane, bis(4-chlorobenzoyl)methane, bis(methylene-3,4-dioxybenzoyl)methane, benzoylacetylphenylmethane, stearoyl(4-methoxybenzoyl)methane, butanoylacetone, distearoylmethane, acetylacetone, stearoylacetone, bis(cyclohexanoyl)-methane, dipivaloylmethane, and the like.

[0042] As the transition metal catalyst (B), manganese stearate, cobalt stearate, manganese 2-ethylhexanoate, cobalt 2-ethylhexanoate, manganese neodecanoate, cobalt neodecanoate, and combinations thereof are preferred, because they are versatile and can efficiently oxidize the ethylene-cyclic olefin copolymer (A).

[0043] The transition metal catalyst (B) is preferably 20 to 10,000 ppm, more preferably 50 to 1,000 ppm, and even more preferably 100 to 500 pm in terms of metal atoms based on the mass of the ethylene-cyclic olefin copolymer (A). If the content of the transition metal catalyst (B) is less than 20 ppm in terms of metal atoms, the oxygen absorption of the resulting resin composition may be insufficient. If the content of the transition metal catalyst (B) is more than 10,000 ppm in terms of metal atoms, the transition metal catalyst (B) may aggregate in the resulting resin composition, causing foreign matter or streaks, resulting in a poor appearance.

[0044] The resin composition of the present invention is also characterized in that the content X (ppm) of the transition metal catalyst (B) calculated as a metal atom and the substituent R in all monomer units constituting the ethylene-cyclic olefin copolymer (A) are 1 The ratio (X / Y) of the content ratio Y (mol%) of the norbornene unit having the following relational formula (IV): 11≦X / Y≦10000 (IV) It is preferable that the ratio (X / Y) is 30 or more and 3000 or less, more preferably 100 or more and 1000 or less. When the ratio (X / Y) is in the above range, sufficient oxygen absorption is obtained while maintaining a good appearance of the molded article. In formula (IV), when the ratio (X / Y) is less than 11, a sufficient oxygen absorption rate may not be obtained. When the ratio (X / Y) exceeds 10000, the hue of the obtained resin composition may deteriorate, or the transition metal catalyst (C) may aggregate in the resin composition, causing foreign matter or streaks, resulting in a deteriorated appearance.

[0045] Alternatively, the resin composition of the present invention may be obtained by adjusting the content X (ppm) of the transition metal catalyst (B) in terms of metal atoms and the number of substituents R in all monomer units constituting the ethylene-cyclic olefin copolymer (A). 1 and the content ratio Y (mol %) of norbornene units having the substituent R 2 The ratio (X / (Y+Z)) of the ethylene unit content Z (mol%) having the following formula (V): 0.1≦X / (Y+Z)≦150 (V) It is preferable that the ratio (X / (Y+Z)) satisfies the above. The ratio (X / (Y+Z)) is more preferably 1.5 or more and 100 or less, and even more preferably 10 or more and 40 or less. When the ratio (X / (Y+Z)) is within the above range, sufficient oxygen absorption is obtained without generating an unpleasant odor. In formula (V), when the ratio (X / (Y+Z)) is less than 0.1, a sufficient oxygen absorption rate may not be obtained. When the ratio (X / (Y+Z)) exceeds 150, an unpleasant odor may be generated during oxygen absorption.

[0046] (EVOH(C)) The resin composition of the present invention may further contain EVOH (C) in addition to the ethylene-cyclic olefin copolymer (A) and the transition metal catalyst (B).

[0047] EVOH (C) can be obtained, for example, by saponifying an ethylene-vinyl ester copolymer. The production and saponification of the ethylene-vinyl ester copolymer can be carried out by a known method. Examples of vinyl esters that can be used in this method include fatty acid vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl pivalate, and vinyl versatate.

[0048] In the present invention, the ethylene content of EVOH (C) is preferably 5 to 60 mol%, more preferably 15 to 55 mol%, and even more preferably 20 to 50 mol%. If the ethylene content is less than 5 mol%, the melt formability and oxygen barrier property at high temperatures tend to decrease. If the ethylene unit content is more than 60 mol%, the oxygen barrier property tends to decrease. The ethylene unit content of such EVOH (C) can be measured, for example, by a nuclear magnetic resonance (NMR) method.

[0049] In the present invention, the lower limit of the saponification degree of the vinyl ester component of EVOH (C) is preferably 90 mol% or more, more preferably 95 mol% or more, and even more preferably 99 mol% or more. By making the saponification degree 90 mol% or more, for example, the oxygen barrier property of the resin composition can be improved. On the other hand, the upper limit of the saponification degree of the vinyl ester component of EVOH (C) may be, for example, 100 mol% or less, or 99.99 mol% or less. The saponification degree of EVOH (C) is 1 The degree of saponification of EVOH (C) can be calculated by measuring the peak area of ​​the hydrogen atom contained in the vinyl ester structure and the peak area of ​​the hydrogen atom contained in the vinyl alcohol structure by H-NMR measurement. When the degree of saponification of EVOH (C) is within the above range, good oxygen barrier property can be provided to the resin composition of the present invention.

[0050] EVOH (C) may also have units derived from other monomers other than ethylene and vinyl esters and saponified products thereof, as long as the object of the present invention is not hindered. When EVOH (C) has such other monomer units, the upper limit of the content of the other monomer units relative to the total structural units of EVOH (C) is, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less, or 5 mol% or less. Furthermore, when EVOH (C) has units derived from the other monomers, the lower limit of the content is, for example, 0.05 mol% or more, or 0.1 mol% or more.

[0051] Other monomers that may be contained in EVOH (C) include, for example, alkenes such as propylene, butylene, pentene, and hexene; 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl ...propene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-1-propene, 3,4-dia 4-Acyloxy-4-methyl-1-butene, 4-Acyloxy-2-methyl-1-butene, 4-Acyloxy-3-methyl-1-butene, 3,4-Diacyloxy-2-methyl-1-butene, 4-Acyloxy-1-pentene, 5-Acyloxy-1-pentene, 4,5-Diacyloxy-1-pentene, 4-Acyloxy-1-hexene, 5-Acyloxy-1-hexene, 6-Acyloxy-1-hexene, 5,6 ester group-containing alkenes or saponification products thereof, such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, and other unsaturated acids or their anhydrides, salts, or mono- or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids or salts thereof, such as vinyl sulfonic acid, allyl sulfonic acid, and methallylsulfonic acid; vinyl silane compounds such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxy-ethoxy) silane, and γ-methacryloxypropyl methoxy silane; alkyl vinyl ethers, vinyl ketones, N-vinyl pyrrolidone, vinyl chloride, and vinylidene chloride.

[0052] The EVOH (C) may be an EVOH modified by a technique such as urethanization, acetalization, cyanoethylation, oxyalkylenation, etc. Such modified EVOH tends to improve the melt moldability of the resin composition of the present invention.

[0053] As the EVOH (C), two or more kinds of EVOHs differing in ethylene unit content, degree of saponification, copolymer components, presence or absence of modification or type of modification may be used in combination.

[0054] EVOH (C) can be obtained by a known method such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. In one embodiment, a bulk polymerization method or a solution polymerization method is used in which polymerization can proceed without a solvent or in a solution such as an alcohol.

[0055] The solvent used in the solution polymerization method is not particularly limited, and is, for example, an alcohol, preferably a lower alcohol such as methanol, ethanol, propanol, etc. The amount of the solvent used in the polymerization reaction liquid may be selected in consideration of the viscosity average degree of polymerization of the target EVOH (C) and chain transfer of the solvent, and the mass ratio of the solvent to the total monomers (solvent / total monomers) contained in the reaction liquid is, for example, 0.01 to 10, and preferably 0.05 to 3.

[0056] Examples of the catalyst used in the polymerization include azo initiators such as 2,2-azobisisobutyronitrile, 2,2-azobis-(2,4-dimethylvaleronitrile), 2,2-azobis-(4-methoxy-2,4-dimethylvaleronitrile), and 2,2-azobis-(2-cyclopropylpropionitrile); and organic peroxide initiators such as isobutyryl peroxide, cumyl peroxy neodecanoate, diisopropyl peroxycarbonate, di-n-propyl peroxy dicarbonate, t-butyl peroxy neodecanoate, lauroyl peroxide, benzoyl peroxide, and t-butyl hydroperoxide.

[0057] The polymerization temperature is preferably 20°C to 90°C, more preferably 40°C to 70°C. The polymerization time is preferably 2 hours to 15 hours, more preferably 3 hours to 11 hours. The polymerization rate is preferably 10% to 90% based on the charged vinyl ester, more preferably 30% to 80%. The resin content in the solution after polymerization is preferably 5% to 85%, more preferably 20% to 70%.

[0058] In the above polymerization, after a predetermined period of polymerization or after a predetermined polymerization rate has been reached, a polymerization inhibitor may be added as necessary, and unreacted ethylene gas may be removed by evaporation to remove unreacted vinyl ester.

[0059] Next, an alkali catalyst is added to the copolymer solution to saponify the copolymer. The saponification method may be either continuous or batchwise. Examples of the alkali catalyst that can be added include sodium hydroxide, potassium hydroxide, and alkali metal alcoholates.

[0060] The EVOH (C) after the saponification reaction contains an alkali catalyst, by-product salts such as sodium acetate and potassium acetate, and other impurities. For this reason, it is preferable to remove these by neutralization or washing as necessary. Here, when the EVOH (C) after the saponification reaction is washed with water (e.g., ion-exchanged water) containing almost no specific ions (e.g., metal ions, chloride ions), the by-product salts such as sodium acetate and potassium acetate may not be completely removed, and some may remain.

[0061] In the resin composition of the present invention, the content of EVOH (C) may be 10 to 99.99 mass% based on the total amount of the resin composition, preferably 50 to 99.5 mass%, and more preferably 80 to 99 mass%. If the content of EVOH (C) in the resin composition is less than 10 mass%, the oxygen barrier property of the resulting resin composition may be insufficient. If the content of EVOH (C) is more than 99.99 mass%, the oxygen absorption property of the resulting resin composition may be insufficient.

[0062] (Aluminum Compounds (D)) The resin composition of the present invention may further contain an aluminum compound (D) in addition to the above-mentioned ethylene-cyclic olefin copolymer (A) and transition metal catalyst (B).

[0063] In the resin composition of the present invention, the aluminum compound (D) may be one added as a catalyst or co-catalyst during the synthesis of the ethylene-cyclic olefin copolymer (A) as described above, or may be one newly added separately as an additive.

[0064] When the aluminum compound (D) is contained in the ethylene-cyclic olefin copolymer (A), it may be directly bonded to the polymer chain by a covalent bond, an ionic bond, a coordinate bond, or the like. Examples of the aluminum compound (D) include aluminum metal or oxides containing aluminum; salts (e.g., chlorides, sulfates, nitrates, hydroxides, carboxylates); organic aluminum; and organic aluminoxanes (polyalkylaluminoxanes obtained by reacting trialkylaluminum with water); and the like. One or more types of aluminum compounds may be used in combination. Examples of aluminum oxides include α-alumina, β-alumina, γ-alumina, and the like. Examples of aluminum chlorides include anhydrous aluminum chloride, aluminum chloride (III) hexahydrate, polyaluminum chloride, and the like. Examples of aluminum sulfides include aluminum sulfide. Examples of aluminum carboxylates include aluminum acetate, aluminum formate, aluminum oxalate, aluminum citrate, aluminum malate, aluminum stearate, aluminum tartrate, and the like. Examples of organic aluminum include trimethyl aluminum, triethyl aluminum, tripropyl aluminum, tributyl aluminum, triisobutyl aluminum, dimethyl aluminum chloride, methyl aluminum dichloride, diethyl aluminum chloride, ethyl aluminum dichloride, etc. Examples of organic aluminoxane include polymethyl aluminoxane, polyethyl aluminoxane, polypropyl aluminoxane, polybutyl aluminoxane, polyisobutyl aluminoxane, polymethyl ethyl aluminoxane, polymethyl butyl aluminoxane, polymethyl isobutyl aluminoxane, etc. Among them, organic aluminum and polyalkyl aluminoxane are preferred, and polymethyl aluminoxane and polymethyl isobutyl aluminoxane are more preferred.

[0065] The content of the aluminum compound (D) is preferably 0.1 to 10,000 ppm, more preferably 0.5 to 10,000 ppm, and even more preferably 1 to 50 ppm, calculated as aluminum metal atoms based on the mass of the entire resin composition. When the content of the aluminum compound (D) satisfies such a range, it is possible to obtain a resin composition that suppresses coloration during melt-kneading and molding of the resin composition and exhibits good oxygen absorption properties.

[0066] (Acetic acid adsorbent material (E)) The resin composition of the present invention may further contain an acetic acid adsorbing material (E) in addition to the above-mentioned ethylene-cyclic olefin copolymer (A) and transition metal catalyst (B).

[0067] The term "acetic acid adsorbent material" used in this specification refers to a material capable of adsorbing acetic acid or acetic acid gas that may be generated by the oxidation of a resin, but also includes materials capable of adsorbing other low molecular weight compounds other than acetic acid or acetic acid gas. Low molecular weight compounds that can be adsorbed by the acetic acid adsorbent material (E) are, for example, volatile decomposition products that may be generated as odor components through the oxidation of a resin. Volatile decomposition products that can be adsorbed by the acetic acid adsorbent material (E) are not necessarily limited, but include, for example, acetic acid, acetaldehyde, formic acid, and tert-butyl alcohol, as well as combinations thereof.

[0068] The acetic acid adsorbing material (E) is not necessarily limited, but examples thereof include layered inorganic compounds such as zeolite, silica gel, and hydrotalcite, and polycarbodiimide. Zeolite is preferred because it can efficiently adsorb the volatile decomposition products and is highly versatile. The zeolite preferably has pores of a predetermined size in order to increase the adsorption efficiency of the volatile decomposition products. The average pore diameter of the zeolite is preferably 0.3 to 1 nm, more preferably 0.5 to 0.9 nm. If the average pore diameter of the zeolite is outside the above range, the volatile decomposition products are not efficiently adsorbed by the zeolite, and the unpleasant odor caused by oxygen absorption in the obtained resin composition may not be appropriately reduced.

[0069] Zeolites useful as the acetic acid adsorbing material (E) include, for example, hydrophobic zeolites having a silica / alumina ratio of at least 5. Such zeolites are commercially available, for example, from Tosoh Corporation under the name High Silica Zeolite (HSZ) (registered trademark).

[0070] The content of the acetic acid adsorbing material (E) is preferably 0.1 to 20 mass%, more preferably 0.2 to 10 mass%, and even more preferably 0.5 to 8 mass% based on the total amount of the resin composition. If the content of the acetic acid adsorbing material (E) in the resin composition is less than 0.1 mass%, if volatile decomposition products as described above are generated, it may be difficult to adequately adsorb these compounds in the resin composition and prevent the diffusion of odorous components to the surroundings. If the content of the acetic acid adsorbing material (E) in the resin composition exceeds 20 mass%, the moldability, handling properties, and mechanical properties such as strength and elongation of the molded product obtained from the resin composition may be reduced, and the color and transparency of the molded product may be deteriorated.

[0071] (Antioxidant (F)) The resin composition of the present invention may further contain an antioxidant (F) in addition to the ethylene-cyclic olefin copolymer (A) and the transition metal catalyst (B).

[0072] The antioxidant (F) is, for example, a compound (such as a phenol-based primary antioxidant) that can prevent deterioration of the resin due to oxidation by capturing peroxide radicals generated in the presence of oxygen.

[0073] Examples of the antioxidant (F) include octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,4-bis-(n-octyl)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (e.g., commercially available under the trade name IRGANOX1010 (BASF)), 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenylpropionate), octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, ... Examples of the hydroxypropyl ester include tadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (e.g., commercially available under the trade name IRGANOX1076 (BASF)), N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), 3,5-di-t-butyl-4-hydroxybenzylphosphonate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tris-(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, octylated diphenylamine, 2,4-bis[(octylthio)methyl]-o-cresol, and isooctyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and combinations thereof. Among these, octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate is preferred because of its good dispersibility in the ethylene-cyclic olefin copolymer (A).

[0074] The content of the antioxidant (F) is preferably 0.001 to 1 mass% based on the total amount of the resin composition, more preferably 0.002 to 0.2 mass%, and even more preferably 0.005 to 0.02 mass%. If the content of the antioxidant (F) in the resin composition is less than 0.001 mass%, peroxide radicals generated during storage and in the extruder may cause, for example, an oxidation reaction or a crosslinking reaction of the ethylene-cyclic olefin copolymer (A) to proceed, resulting in poor appearance of the film after pelletization or film formation. If the content of the antioxidant (F) exceeds 1 mass%, oxidation of the ethylene-cyclic olefin copolymer (A) may be suppressed, and the oxygen absorption of the resulting resin composition may be reduced.

[0075] (Other thermoplastic resins (G) and additives (H)) The resin composition of the present invention may contain a thermoplastic resin (G) other than the ethylene-cyclic olefin copolymer (A) and the above EVOH (C) within the range not impairing the effects of the present invention.

[0076] Examples of the thermoplastic resin (G) include polyethylene, polypropylene, ethylene-propylene copolymers, ethylene or propylene copolymers (copolymers of ethylene or propylene with at least one of the following monomers: α-olefins such as 1-butene, isobutene, 4-methyl-1-pentene, 1-hexene, and 1-octene; unsaturated carboxylic acids such as itaconic acid, methacrylic acid, acrylic acid, and maleic anhydride, salts thereof, partial or complete esters thereof, nitriles thereof, amides thereof, and anhydrides thereof; vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl octanoate, and vinyl dodecyl ether. Examples of the other thermoplastic resins (G) include carboxylic acid vinyl esters such as carboxylate, vinyl stearate, and vinyl arachidonate; vinyl silane compounds such as vinyl trimethoxysilane; unsaturated sulfonic acids and their salts; alkylthiols; vinylpyrrolidones; polyolefins such as poly(4-methyl-1-pentene) and poly(1-butene); polyesters such as poly(ethylene terephthalate), poly(butylene terephthalate), and poly(ethylene naphthalate); polystyrene; polycarbonate; and polyacrylates such as polymethyl methacrylate; polyvinyl alcohol; and combinations thereof. The content of the other thermoplastic resins (G) is preferably 30% by mass or less based on the mass of the entire resin composition of the present invention.

[0077] The resin composition of the present invention may contain other additives (H) within a range that does not impair the effects of the present invention. Examples of other additives (H) include viscosity modifiers, plasticizers, photoinitiators, deodorants, UV absorbers, antistatic agents, lubricants, colorants, drying agents, fillers, processing aids, flame retardants, and antifogging agents. The content of other additives (H) is not particularly limited, and an appropriate amount can be selected within a range that does not impair the effects of the present invention.

[0078] Among the other additives (H), in order to improve the processability of the resin composition of the present invention, it is preferable to add a thermoplastic resin having a melt flow rate (MFR) higher than that of the ethylene-cyclic olefin copolymer (A) as a viscosity modifier. As the viscosity modifier, for example, a thermoplastic resin having an MFR of 10 to 1000 g / 10 min at 190° C. and a load of 2160 g is preferable, and specifically, ethylene-vinyl acetate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, high density polyethylene, etc. can be mentioned. When the MFR is within the above range, improvement in processability can be achieved with a small amount of addition. The content is preferably 1 mass % or more and 30 mass % or less based on the mass of the entire resin composition of the present invention. When the amount of the viscosity modifier added is less than 1 mass %, the effect of improving processability is small, and when the amount of the viscosity modifier added is more than 30 mass %, the viscosity is excessively reduced, and there are cases where the film thickness unevenness increases when the multilayer structure is produced.

[0079] (Alkaline earth metal salts (I)) The resin composition of the present invention may further contain an alkaline earth metal salt (I) in addition to the above-mentioned ethylene-cyclic olefin copolymer (A) and transition metal catalyst (B).

[0080] In the resin composition of the present invention, the alkaline earth metal salt (I) may be one that has been added as a catalyst or co-catalyst during the synthesis of the ethylene-cyclic olefin copolymer (A) as described above, and / or may be one that has been added separately as an additive.

[0081] When the alkaline earth metal salt (I) is added as a catalyst or cocatalyst during the synthesis of the ethylene-cyclic olefin copolymer (A), the alkaline earth metal salt (I) may be contained in a state of being directly bonded to the polymer chain of the ethylene-cyclic olefin copolymer (A) by a covalent bond, an ionic bond, a coordinate bond, or the like. Examples of the alkaline earth metal salt (I) include carboxylates. Examples of the carboxylates include magnesium acetate, magnesium formate, magnesium oxalate, magnesium citrate, magnesium malate, magnesium stearate, magnesium tartrate, calcium acetate, calcium formate, calcium oxalate, calcium citrate, calcium malate, calcium stearate, calcium tartrate, and the like. Among them, magnesium acetate, calcium acetate, magnesium stearate, and calcium stearate are preferred.

[0082] The content of the alkaline earth metal salt (I) is preferably 0.1 to 10,000 ppm, more preferably 1 to 1,000 ppm, and even more preferably 10 to 500 ppm in terms of alkaline earth metal atoms based on the mass of the entire resin composition. When the content of the alkaline earth metal salt (I) satisfies such a range, it is possible to obtain a resin composition that suppresses torque increase during melt kneading and molding of the resin composition and exhibits good oxygen absorption properties. In particular, when the resin composition contains EVOH (C), the inclusion of the alkaline earth metal salt (I) is particularly preferred from the viewpoint of improving the oxygen absorption rate.

[0083] The resin composition of the present invention has an oxygen absorption of preferably 0.1 to 300 mL / g, more preferably 0.5 to 200 mL / g, and even more preferably 1.0 to 150 mL / g over 7 days under conditions of 60° C. and 10% RH. When the resin composition of the present invention has an oxygen absorption within such range, the resin composition can maintain high oxygen barrier properties for a long period of time, and a multilayer structure containing the resin composition can maintain high oxygen barrier properties even after retort treatment.

[0084] (2) Production of resin composition The resin composition of the present invention can be produced by mixing the above-mentioned components (A) and (B) with one or more of the components (C) to (F) as necessary. In producing the resin composition of the present invention, the method of mixing these components is not particularly limited, and the order in which the components are mixed is also not particularly limited.

[0085] As a specific method of mixing, a melt kneading method is preferred from the viewpoint of process simplicity and cost. In this case, it is preferable to use an apparatus capable of achieving a high degree of kneading and to disperse each component finely and uniformly, in order to improve the oxygen absorption function and transparency, and to prevent the generation and inclusion of gel particles.

[0086] Examples of devices that can achieve a high degree of kneading include continuous intensive mixers, kneading type twin screw extruders (same direction or different direction), mixing rolls, co-kneaders, and other continuous type kneaders; batch type kneaders such as high speed mixers, Banbury mixers, intensive mixers, and pressure kneaders; devices using rotating disks with a millstone-like grinding mechanism such as KCK kneading extruders manufactured by KCK Corporation, devices equipped with a kneading section (Dulmage, etc.) in a single screw extruder; and simplified kneaders such as ribbon blenders and Brabender mixers. Among these, continuous type kneaders are preferred. In the present invention, it is preferable to adopt devices that connect an extruder and a pelletizer to the discharge port of these continuous kneaders and simultaneously perform kneading, extrusion, and pelletization. A twin screw kneading extruder having a kneading disk or a kneading rotor can also be used. One kneader may be used, or two or more kneaders may be connected and used.

[0087] The kneading temperature is preferably, for example, in the range of 120°C to 300°C. In order to prevent oxidation of the ethylene-cyclic olefin copolymer (A) during the production stage of the resin composition, it is preferable to seal the hopper mouth with nitrogen and extrude at a low temperature. The kneading time is not particularly limited, and an appropriate time can be appropriately selected by a person skilled in the art depending on the types and amounts of the components (A) to (H) used.

[0088] (3) Multilayer structure The above resin composition can be used as an oxygen absorbing layer of a multi-layer structure.

[0089] In one embodiment, the multilayer structure has a layer structure such as x / y, x / y / x, x / z / y, x / z / y / z / x, x / y / x / y / x / x, x / z / y / z / x / z / y / z / x / z / y / z / x, or x / z / y / z / x / z / y / z / x / z / x, where x is an x-layer, but is not limited to these.

[0090] When a plurality of x layers are provided in the multilayer structure, the types of the x layers may be the same or different. A layer using recycled resin made of scraps such as trim generated during molding may be provided separately, or a layer may be formed from a recycled resin blended with another resin. The thickness of each layer in the multilayer structure is not particularly limited, but in order to obtain good moldability and cost, the thickness ratio of the y layer to the total layer thickness is preferably 2 to 20%.

[0091] The resin constituting the x layer is preferably a thermoplastic resin from the viewpoint of processability. Examples of the thermoplastic resin that can be used for the x layer include polyethylene, polypropylene, ethylene-propylene copolymers, ethylene or propylene copolymers (copolymers of ethylene or propylene with at least one of the following monomers: α-olefins such as 1-butene, isobutene, 4-methyl-1-pentene, 1-hexene, and 1-octene; ethylene-vinyl acetate copolymers; unsaturated carboxylic acids such as itaconic acid, methacrylic acid, acrylic acid, and maleic anhydride, salts thereof, partial or complete esters thereof, nitriles thereof, amides thereof, and anhydrides thereof; vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl octanoate, vinyl dodecanoate, Examples of the thermoplastic resin layer include vinyl esters of carboxylic acids such as vinyl stearate and vinyl arachidonate; vinyl silane compounds such as vinyl trimethoxysilane; unsaturated sulfonic acids or salts thereof; alkyl thiols; vinyl pyrrolidones; polyolefins such as poly4-methyl-1-pentene and poly1-butene; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyamides such as polyε-caprolactam, polyhexamethylene adipamide, and polymetaxylylene adipamide; polyvinylidene chloride, polyvinyl chloride, polystyrene, polyacrylonitrile, polycarbonate, and polyacrylate. Such a thermoplastic resin layer may be unstretched, or may be uniaxially or biaxially stretched or rolled.

[0092] In the above thermoplastic resin layer structure, the layers other than the oxygen absorbing layer are preferably made of a resin having relatively high gas permeability and hydrophobicity as the resin forming the inner layer of the multilayer structure, from the viewpoint of facilitating the absorption of oxygen inside the multilayer structure. In addition, it is preferable that the resin is heat-sealable depending on the application of the multilayer structure. Examples of such resins include polyolefins such as polyethylene and polypropylene, and ethylene-vinyl acetate copolymers. On the other hand, it is preferable that the outer layer of the multilayer structure is made of a resin having excellent moldability and mechanical properties. Examples of such resins include polyolefins such as polyethylene and polypropylene, polyamides, polyesters, polyethers, and polyvinyl chloride.

[0093] When the multilayer structure of the present invention is used as a packaging material such as a container, it is preferable that the multilayer structure further includes a gas barrier resin layer made of polyamide, ethylene-vinyl alcohol copolymer, or the like in order to prevent oxygen from entering the packaging material from the outside. The gas barrier resin layer may also include the above-mentioned resin composition of the present invention, and from the viewpoint of efficiently absorbing and removing oxygen present inside the package, it is preferable that an oxygen absorbing layer containing the above-mentioned resin composition is disposed between the gas barrier resin layer and the contents. Furthermore, another layer may be included between the oxygen absorbing layer and the layer made of the gas barrier resin.

[0094] For example, when the multilayer structure of the present invention is used as a retort packaging material or a container lid material, the thermoplastic resin constituting the outer layer is polyamide, polyester, or polyolefin such as polypropylene, and polypropylene is particularly preferably used. Polypropylene is preferably used for the inner layer. Polyolefin is preferred in terms of moisture resistance, mechanical properties, economical efficiency, heat sealability, etc. Polyester is preferred in terms of mechanical properties, heat resistance, etc.

[0095] When the multilayer structure of the present invention is used as a packaging material for retort pouches, it is preferred to provide layers with high water vapor barrier properties on both sides of the oxygen absorbing layer or on the side that will be subject to high humidity during use of the packaging material, since the multilayer structure is exposed to high humidity when used as a packaging material for retort pouches. A molded product provided with such layers has a particularly extended duration of oxygen absorbing performance, and therefore maintains extremely high gas barrier properties for a longer period of time.

[0096] The adhesive resin used for the z layer is not particularly limited as long as it can bond each layer, and polyurethane-based or polyester-based one-component or two-component curing adhesives, carboxylic acid-modified polyolefin resins, etc. are preferably used. Examples of carboxylic acid-modified polyolefin resins include olefin polymers or copolymers containing unsaturated carboxylic acids or their anhydrides (such as maleic anhydride) as copolymerization components; or graft copolymers obtained by grafting unsaturated carboxylic acids or their anhydrides to olefin polymers or copolymers. Among them, carboxylic acid-modified polyolefin resins are preferred. In particular, when the x layer is a polyolefin resin, using a carboxylic acid-modified polyolefin resin for the z layer improves the adhesion with the y layer. Examples of carboxylic acid-modified polyolefin resins include polyethylene (e.g., low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and very low-density polyethylene (VLDPE)), polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymer, and ethylene-(meth)acrylic acid ester (methyl ester or ethyl ester) copolymers modified with carboxylic acid.

[0097] Examples of methods for obtaining the multilayer structure of the present invention include extrusion lamination, dry lamination, co-injection molding, co-extrusion molding, etc. Examples of co-extrusion molding methods include co-extrusion lamination, co-extrusion sheet molding, co-extrusion inflation molding, co-extrusion blow molding, etc. Examples of multilayer structures obtained by such methods include sheets, films, parisons, etc.

[0098] (4)Applications The sheet, film, parison, etc. of the multilayer structure of the present invention can be reheated at a temperature equal to or lower than the melting point of the resin contained in the multilayer structure, and uniaxially or biaxially stretched by a thermoforming method such as squeeze molding, a roll stretching method, a pantograph stretching method, an inflation stretching method, a blow molding method, or the like, to obtain a desired molded product.

[0099] The obtained molded article can be used, for example, as a packaging material for packaging a predetermined content.

[0100] The packaging material has excellent oxygen absorption properties, and is very little prone to odor generation and migration to the contents due to oxidation caused by volatile decomposition products, and can be suitably used for packaging contents that are prone to some deterioration due to the influence of oxygen. Examples of such contents include food (e.g., fresh foods, processed foods, refrigerated foods, frozen foods, freeze-dried foods, prepared foods, semi-prepared foods, etc.); beverages (e.g., drinking water, tea drinks, dairy drinks, processed milk, soy milk, coffee, cocoa, soft drinks, soups, alcoholic beverages (e.g., beer, wine, shochu, sake, whiskey, brandy, etc.); pet foods (e.g., dog foods, cat foods); feed or feed for livestock, poultry, and farmed fish; oils and fats (e.g., edible oils, industrial oils, etc.); pharmaceuticals (e.g., pharmacy medicines, prescription medicines, general medicines, and veterinary medicines); and other drugs. The multilayer structure of the present invention is particularly preferably used as a food package because the contents are susceptible to deterioration, spoilage, and the like due to the influence of oxygen, and there is a great need for a packaging material with excellent oxygen absorption properties. EXAMPLES

[0101] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0102] Example I: Preparation of oxygen absorbing films and multilayer structures (Ia) Evaluation of oxygen absorption 100 mg of the oxygen-absorbing films obtained in Examples I-1 to I-24 and Comparative Examples I-1 to I-5 were cut out as samples, placed in a 35.5 mL pressure-resistant glass bottle under air, sealed with an aluminum cap equipped with a Naflon rubber packing, and stored for 14 days under conditions of 40°C and 22% RH. The oxygen concentration in the container after storage was measured using a Packmaster (manufactured by Iijima Electronics Co., Ltd.).

[0103] (Ib) Odor evaluation after oxygen absorption Samples prepared in the same manner as above (Ia) and stored in the same manner were opened, and the odor inside the container was judged by five experts using the following criteria, and the average score of the judgment results was calculated. The lower the score, the less the odor. 5: I noticed a strong, unpleasant odor that made me choke. 4: I noticed a strong, unpleasant odor that made me want to hold my nose. 3: Sufficient unpleasant odor was felt. 2: A weak unpleasant odor was detected. 1: A slightly unpleasant odor was detected. 0: No unpleasant odor was felt at all.

[0104] (Ic) Analysis of odor components after oxygen absorption A sample prepared in the same manner as in (Ia) above was placed in a pressure-resistant glass bottle equipped with a fluorescent oxygen concentration sensor under air, sealed with an aluminum cap equipped with a Teflon (registered trademark) rubber packing, and stored at 60°C for one day in Example 1, and at 60°C for three days in Comparative Example I-3, to allow the sample to absorb 2.5cc of oxygen, a portion of the oxygen in the glass container. The fact that the sample had absorbed 2.5cc of oxygen was confirmed by monitoring the oxygen concentration in the container with a portable non-destructive oxygen meter Fibox4 trace (manufactured by PreSens) and finding that the oxygen concentration had decreased from 20.9% to 14.9%. Next, with the glass bottle held at 60°C, 1.5 cc of the gas in the container after storage was taken out using a gas-tight syringe heated to 60°C, and the gas was introduced into a GC-MS (GC system 7890B, detector 5977B MSD, manufactured by Agilent Technologies, column: DB-624 (column length: 60 m, column diameter: 0.25 mm, manufactured by Agilent Technologies), heating conditions: held at 40°C for 5 minutes, heated to 150°C at 5°C / min, and then heated to 250°C at 10°C / min) to analyze the generated gas components.

[0105] (Id) Measurement of MFR (Melt Flow Rate) The MFR of the ethylene-cyclic olefin copolymer (A), the viscosity modifier, and the resin composition obtained by twin-screw kneading was measured at 190° C. under a load of 2160 g using a melt flow indexer.

[0106] (Example I-1: Preparation of oxygen absorbing film) 100 parts by mass of EPDM elastomer (Dow Chemical Company's "NORDEL IP4770P", Mw = 200,000, MFR = 0.07g / 10 min) composed of ethylene, propylene, and 5-ethylidene-2-norbornene monomers was mixed with 0.4 parts by mass of manganese stearate as a transition metal catalyst (B), and melt-kneaded in a twin-screw kneading extruder (screw diameter 25 mmφ, L / D = 30, Toyo Seiki Seisakusho Co., Ltd.) under conditions of a cylinder temperature of 230°C and a screw rotation speed of 50 rpm. The mixture was then extruded from the die into a cooling water tank at 5°C in the form of strands, and pelletized with a strand cutter to obtain pellets.

[0107] The pellets were then placed in a single-layer extruder (screw diameter 20 mmφ, L / D=20, manufactured by Toyo Seiki Seisakusho Co., Ltd.), melt-kneaded at a cylinder temperature of 230°C and a screw rotation speed of 40 rpm, and cast from the die onto a cooling roll at 20°C to obtain an oxygen-absorbing film with a thickness of 20 μm.

[0108] Using this oxygen absorbing film, the above-mentioned oxygen absorbing property and odor after oxygen absorption were evaluated. In addition, the odor components after oxygen absorption were analyzed by GC-MS. The composition of this oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3. The GC-MS graph of evaluation (Ic) is shown in Figure 1.

[0109] (Examples I-2 to I-6: Preparation of oxygen absorbing films) An oxygen absorbing film was produced and various evaluations were carried out in the same manner as in Example I-1, except that the ethylene-cyclic olefin copolymer (A) was changed to an EDPM elastomer composed of the monomer units shown in Table 1. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0110] The EDPM elastomers listed in the Type column in Table 1 correspond to the following products: "NORDEL IP3745P" (Dow Chemical Company, Mw=140,000, MFR=0.2g / 10min) "NORDEL IP4820P" (Dow Chemical Company, Mw=75,000, MFR=1g / 10min) "Mitsui EPT K-9720" (Mitsui Chemicals, Inc., Mw=60,000, MFR=2g / 10min) "Mitsui EPT X-3012P" (Mitsui Chemicals, Inc., MFR=5g / 10min) "RoyalEdge5041" (Lion Copolymer Geismar)

[0111] (Example I-7: Preparation of oxygen absorbing film) Except for changing the ethylene-cyclic olefin copolymer (A) to "ESPRENE 301A" (EPDM elastomer, Mw=210,000) manufactured by Sumitomo Chemical Co., Ltd., cutting the veiled Esprene 301A into 0.5 cm squares and feeding them into the twin-screw extruder, and changing the transition metal catalyst (B) to cobalt stearate, an oxygen absorbing film was produced in the same manner as in Example I-1, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0112] (Example I-8: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-1, except that the ethylene-cyclic olefin copolymer (A) was changed to an ethylene-norbornene copolymer ("TOPAS E-140" manufactured by Polyplastics Co., Ltd.), and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0113] (Example I-9: Preparation of oxygen absorbing film) Except for changing the transition metal catalyst (B) to cobalt stearate, an oxygen absorbing film was produced in the same manner as in Example I-1, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0114] (Example I-10: Preparation of oxygen absorbing film) Except for changing the content of cobalt stearate to 0.021 parts by mass, an oxygen absorbing film was produced in the same manner as in Example I-9, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0115] (Example I-11: Preparation of oxygen absorbing film) Except for changing the content of cobalt stearate to 1.073 parts by mass, an oxygen absorbing film was produced in the same manner as in Example I-9, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0116] (Example I-12: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-1, except that the amount of manganese stearate added was changed to 0.416 parts by mass, and 4 parts by mass of zeolite having an average pore size of 0.9 nm ("Zeolum F-9" manufactured by Tosoh Corporation) was mixed with the EPDM elastomer and manganese stearate as the acetic acid adsorbent (C) and melt-kneaded in a twin-screw extruder, and various evaluations were performed. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0117] (Examples I-13 to I-16: Preparation of oxygen absorbing films) Except for changing the amount of manganese stearate added and the type and content of the acetic acid adsorbent (C) as shown in Tables 2 and 3, oxygen absorbing films were prepared and various evaluations were carried out in the same manner as in Example I-12. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0118] The products listed in the type column of acetic acid adsorbent (C) in Table 2 correspond to the following: "HSZ940HOA" (high silica zeolite manufactured by Tosoh Corporation) Average pore size: 0.65 nm "Carbodilite LA-1" (polycarbodiimide manufactured by Nisshinbo Chemical Inc.) "Silysia 310P" (amorphous silica gel manufactured by Fuji Silysia Chemical Ltd.) Average particle size: 2.7 μm, average pore size: 21 nm

[0119] (Example I-17: Preparation of oxygen absorbing film) Except for changing the amount of ethylene-cyclic olefin copolymer (A) to 80 parts by mass, and further mixing 20 parts by mass of partially hydrogenated styrene butadiene rubber ("Tuftec P1083" manufactured by Asahi Kasei Chemicals Corporation) as another thermoplastic resin (G) with the EPDM elastomer and manganese stearate, and melt-kneading them in a twin-screw extruder, an oxygen absorbing film was produced in the same manner as in Example I-1, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0120] (Example I-18: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-17, except that 8 parts by mass of high-silica zeolite "HSZ940HOA" was further added as an acetic acid adsorbent (C), mixed, and melt-kneaded in a twin-screw extruder, and various evaluations were performed. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0121] (Example I-19: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-17, except that the amount of ethylene-cyclic olefin copolymer (A) added was changed to 80 parts by mass, and 20 parts by mass of an ethylene-vinyl acetate copolymer ("Evaflex V56113" manufactured by Mitsui Chemicals, Inc. (vinyl acetate content = 20 wt%, MFR = 20 g / 10 min) was further added as another thermoplastic resin (G) together with the EPDM elastomer and manganese stearate, and the mixture was melt-kneaded in a twin-screw extruder. Various evaluations were performed. By adding the ethylene-vinyl acetate copolymer with a high MFR, the MFR of the resin composition obtained by twin-screw kneading became 0.2 g / 10 min, and the oxygen absorbing film could be efficiently formed with a lower torque when extruding it compared to Example I-1. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of the evaluations (Ia) and (Ib) are shown in Table 3.

[0122] (Example I-20: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-4, except that 0.01 parts by mass of octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (BASF's "Irganox 1076") as the antioxidant (F) was mixed with the EPDM elastomer and manganese stearate and melt-kneaded in a twin-screw extruder, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0123] (Examples I-21 and I-22: Preparation of oxygen absorbing films) Except for changing the content of the antioxidant (F) as shown in Tables 2 and 3, oxygen-absorbing films were prepared and various evaluations were carried out in the same manner as in Example I-21. The composition of the oxygen-absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0124] (Example I-23: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-5, except that the amount of EPDM elastomer "Mitsui EPT X-3012P" added was changed to 20 parts by mass, and 80 parts by mass of 1-hexene modified L-LDPE ("Harmolex NF325N" manufactured by Japan Polyethylene Co., Ltd.) was further mixed with the EPDM elastomer and manganese stearate and melt-kneaded in a twin-screw extruder, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0125] (Example I-24: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-24, except that the amount of EPDM elastomer "Mitsui EPT X-3012P" and the amount of 1-hexene modified L-LDPE ("Harmolex NF325N" manufactured by Japan Polyethylene Co., Ltd.) added were changed to 50 parts by mass, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0126] (Comparative Example I-1: Preparation of oxygen absorbing film) Except for changing the ethylene-cyclic olefin copolymer (A) to an ethylene-norbornene copolymer ("TOPAS 6013" manufactured by Polyplastics Co., Ltd.), an oxygen absorbing film was produced in the same manner as in Example I-1, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0127] (Comparative Example I-2: Preparation of oxygen absorbing film) Except for using 1-hexene modified L-LDPE ("Harmolex NF325N" manufactured by Japan Polyethylene Co., Ltd.) instead of EPDM elastomer, an oxygen absorbing film was produced in the same manner as in Example I-1 and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0128] (Comparative Example I-3: Preparation of oxygen absorbing film) Except for using ethylene-octene copolymer ("ENGAGE8407" manufactured by Dow Chemical Company) instead of EPDM elastomer, oxygen absorbing films were prepared in the same manner as in Example I-1, and various evaluations were carried out. The composition of the oxygen absorbing films is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3. The GC-MS graph of evaluation (Ic) is shown in Figure 1.

[0129] (Comparative Example I-4: Preparation of oxygen absorbing film) Except for not adding manganese stearate, an oxygen absorbing film was prepared in the same manner as in Example I-2, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0130] (Comparative Example I-5: Preparation of oxygen absorbing film) An oxygen absorbing film was produced in the same manner as in Example I-1, except that isoprene rubber ("IR2200" manufactured by JSR Corporation) was used instead of the EPDM elastomer, and bales of isoprene rubber IR2200 were cut into 0.5 cm squares and fed into the twin-screw extruder, and various evaluations were carried out. The composition of the oxygen absorbing film is shown in Tables 1 and 2, and the results of evaluations (Ia) and (Ib) are shown in Table 3.

[0131] (Example I-25: Preparation of multi-layer structure) Metallocene L-LDPE (Ube Maruzen Polyethylene Co., Ltd., "Yumerit 3540N") was used as the base resin in the first extruder, maleic anhydride modified linear low-density polyethylene (Mitsui Chemicals, Inc., "Admer NF-539") was used as the adhesive resin in the second extruder, and resin composition pellets containing the EPDM elastomer "Mitsui EPT K-9720P" prepared in Example I-3 as the oxygen absorbing resin were used in the third extruder. F101B" was fed into the fourth extruder, and a four-type, six-layer multilayer extruder was used to produce a four-type, six-layer multilayer film with a layer structure of L-LDPE (30 μm) / oxygen absorbing layer (20 μm) / adhesive layer (10 μm) / EVOH (20 μm) / adhesive layer (10 μm) / L-LDPE (30 μm) under conditions of an extrusion temperature of 180-220°C and a die temperature of 220°C.

[0132] The obtained multilayer film was cut into a size of 22 cm × 12 cm, and 1 cm of each edge of each of the four sides was heat-sealed at 150 °C to obtain an air-filled inner volume of 100 mL and an inner surface area of ​​200 cm. 2 A pouch-shaped multilayer structure was produced. The multilayer structure was stored at 40°C for two weeks, after which the oxygen concentration inside the pouch was measured using a Packmaster (manufactured by Iijima Electronics Co., Ltd.) to evaluate the oxygen absorption of the multilayer structure. A pouch produced in the same manner was opened after two weeks of storage, and the odor inside the multilayer structure after oxygen absorption was evaluated by five experts who each judged the odor inside the pouch according to the following criteria, and the average score of the obtained judgment results was calculated. The lower the score, the less the odor. 5: I noticed a strong, unpleasant odor that made me choke. 4: I noticed a strong, unpleasant odor that made me want to hold my nose. 3: Sufficient unpleasant odor was felt. 2: A weak unpleasant odor was detected. 1: A slightly unpleasant odor was detected. 0: No unpleasant odor was felt at all.

[0133] The composition of the multilayer structure constituting this pouch is shown in Tables 1 and 2, and the results are shown in Table 4.

[0134] (Comparative Example I-6: Preparation of a multilayer structure) In the multi-layer extrusion of four kinds and six layers, except that the resin composition pellets containing the ethylene-norbornene copolymer ("TOPAS 6013" manufactured by Polyplastics Co., Ltd.) prepared in Comparative Example I-1 were added to the third extruder as the oxygen-absorbing resin, a four-kind, six-layer oxygen-absorbing film and a pouch using the same were prepared in the same manner as in Example I-25, and the oxygen absorption of the multi-layer structure and the odor in the pouch after oxygen absorption were evaluated. The composition of the multi-layer structure constituting this pouch is shown in Tables 1 and 2, and the above results are shown in Table 4.

[0135] [Table 1]

[0136] [Table 2]

[0137] [Table 3]

[0138] [Table 4]

[0139] As shown in Table 3, for example, compared to the film of Comparative Example I-1, the oxygen absorbing films produced in Examples I-1 to I-24 all had low oxygen concentrations in the above evaluation, and the numerical values ​​of the oxygen absorption of the films were high. Such low oxygen concentrations were also found in Comparative Examples I-2 and I-5, but the results of the odor evaluation (sensory evaluation) were all high. Regarding this odor evaluation, the oxygen absorbing films produced in Examples I-1 to I-25 all showed low values, and it can be seen that the oxygen absorbing films produced in Examples I-1 to I-24 have excellent oxygen absorption properties and also suppress the generation of odor caused by volatile decomposition products after oxygen absorption.

[0140] Focusing on the types of volatile decomposition products remaining after oxygen absorption, as shown in Figure 1, the oxygen-absorbing film produced in Example I-1 has an extremely small number of types of volatile decomposition products remaining after oxygen absorption compared to the film produced in Comparative Example I-3, and only acetaldehyde, tert-butyl alcohol, and acetic acid were detected at most by GC-MS. In particular, fatty acids with 4 or more carbon atoms, which have a strong odor and were detected in Comparative Example I-3, were not detected at all in Example I-1.

[0141] As shown in Table 4, the multilayer structure produced in Example I-25 also had a lower oxygen concentration in the above evaluation and a higher oxygen absorption value in the produced pouch compared to the multilayer structure of Comparative Example I-6. Also, in the odor evaluation, the multilayer structure produced in Example I-25 had a sufficiently weak unpleasant odor. From this, it can be seen that the multilayer structure produced in Example I-25 also had excellent oxygen absorption properties, and the generation of odor caused by volatile decomposition products after oxygen absorption was also suppressed.

[0142] Example II: Preparation of Pellets, Oxygen Absorbing Film and Thermoformed Cups (II-a) Compositional evaluation of ethylene-cyclic olefin copolymer (A) The ethylene-cyclic olefin copolymers (A) synthesized in Examples II-1 to II-16 and Comparative Examples II-1 to II-3 were dissolved in 1,2-dichlorobenzene-d4 (deuterated solvent) containing 1.5% by mass of chromium (III) acetylacetonate, and heated at 130° C. 1 The composition of the copolymerization ratio was analyzed by 1 H NMR (Nuclear Magnetic Resonance Spectrometer, JEOL, 600 MHz, TMS as the reference peak). The contents of butyl, pentyl, and hexyl groups, which are trace branching components generated during polymerization, were analyzed by the same method. 13 The content was determined by C NMR analysis. Specifically, the content of trace branched components was determined from the amount of methylene groups one to the butyl terminal carbon (peak appearing at 22.8 ppm), the amount of methylene groups two to the pentyl terminal carbon (peak appearing at 33.2 ppm), and the amount of methylene groups two to the hexyl terminal carbon (peak appearing at 32.1 ppm) relative to the integral value of all carbon atoms measured excluding signals derived from the solvent.

[0143] (II-b) Melt flow rate (MFR) of ethylene-cyclic olefin copolymer (A) The ethylene-cyclic olefin copolymers (A) synthesized in Examples II-1 to II-16 and Comparative Examples II-1 to II-3 were subjected to measurement of the flow rate (g / 10 min) of the samples using a melt indexer ("L244" manufactured by Takara Kogyo Co., Ltd.) under conditions of a temperature of 190°C and a load of 2160 g to obtain the melt flow rate.

[0144] (II-c) Analysis of the amount of aluminum metal contained in the resin composition or ethylene-cyclic olefin copolymer (A) To 0.1 g of the resin composition or ethylene-cyclic olefin copolymer (A) obtained in Examples II-1 to II-16, 1 mL of concentrated nitric acid (specific gravity 1.38 g / mL) was added, and the mixture was left at room temperature for 60 minutes or more, and then subjected to wet decomposition using microwaves. The mixture was further diluted with pure water to adjust the solution concentration, and quantitative analysis was performed using ICP-MS.

[0145] (II-d) Evaluation of oxygen absorption 200 mg of the oxygen absorbing film having a thickness of 20 μm obtained in Examples II-17 to II-32 and Comparative Examples II-4 to II-6 was cut out as a sample, placed in a pressure-resistant glass bottle having an internal volume of 35.5 mL at 23°C and a humidity of 65%, sealed with an aluminum cap with a Naflon rubber packing, and stored at 60°C for 7 days. The humidity inside the container during storage at 60°C was 10% based on the amount of water vapor in the air at the time of preparation. The oxygen concentration inside the container after storage was measured using a Packmaster (manufactured by Iijima Electronics Co., Ltd.) at 23°C and a humidity of 65%.

[0146] (II-e) Evaluation of odor after oxygen absorption Samples prepared in the same manner as above (II-d) and stored under the same conditions for the same period were opened at room temperature of 23°C, and the odor inside the container was judged by five experts using the following criteria, and the average score of the judgment results was calculated. The lower the score, the less the odor. 5: A strong, unpleasant odor was detected that made it impossible to sniff for more than one second. 4: I could only sniff for 1 to 3 seconds and felt like I wanted to pinch my nose. 3: Able to sniff for more than 3 seconds, but detects a distinctly unpleasant odor. 2: A weak unpleasant odor was detected. 1: There was no unpleasant odor when I first smelled it, but when I smelled it again carefully, I detected a slightly unpleasant odor. 0: No unpleasant odor was felt at all.

[0147] (II-f) Analysis of odor components (butyric acid and valeraldehyde production) after oxygen absorption The sample prepared in the same manner as in (II-d) above was stored at 60°C for 7 days. Then, while the glass bottle was kept at 60°C, 1.5 cc of the gas in the container after storage was taken out with a gas-tight syringe heated to 60°C, and analyzed by GC-MS (GC system 7890B, detector 5977B The butyric acid and valeraldehyde components generated were analyzed by feeding the sample into an MSD (manufactured by Agilent Technologies), column: DB-624 (column length: 60 m, column diameter: 0.25 mm, manufactured by Agilent Technologies, heating conditions: held at 40°C for 5 minutes, heated to 150°C at 5°C / min, and then heated to 250°C at 10°C / min). The detection time for butyric acid was 25 minutes 30 seconds, and the detection time for valeraldehyde was 20 minutes 10 seconds. For samples in which the generation of butyric acid and valeraldehyde was confirmed from the results of mass spectrometry performed simultaneously with the measurement of each sample, the amount of butyric acid and valeraldehyde generated (ppm) was quantified using a calibration curve created in advance. The detection limit for each component was 5 ppm, and when the peak intensity was 5 ppm or less, it was considered to be below the detection limit. Note that butyric acid and valeraldehyde are compounds that emit a strong odor even in small amounts, and the smaller the amount of these compounds generated, the less odor the material generates after oxygen absorption, which is preferable.

[0148] (II-g) Analysis of dissolved oxygen concentration before and after retort treatment The thermoformed cups produced in Examples II-33 to II-48 and Comparative Examples II-7 to II-9 were filled to the brim with ion-exchanged water in which the dissolved oxygen concentration had been reduced to 1.5 ppm by nitrogen bubbling, and a cover material (a biaxially oriented polypropylene film of 50 μm, a biaxially oriented nylon film of 50 μm, and an oxygen / water vapor high barrier film (Kuraray's "Kurarista C") of 12 μm, dry-laminated in this order) to which an oxygen concentration sensor was attached was heat-sealed so that the biaxially oriented polypropylene side was the cup side, sealing the ion-exchanged water. After measuring the dissolved oxygen concentration at room temperature of 20°C, hot water retort treatment was performed for 30 minutes under conditions of a temperature of 120°C and a gauge pressure of 0.17 MPa. After the retort treatment, the water was wiped off, and the cup was left to cool for 4 hours in a room at room temperature of 20°C, and the dissolved oxygen concentration after the retort treatment was measured.

[0149] (II-h) Pellet color The hues (YI value, b value) of the pellets obtained in Examples II-1 to II-16 and Comparative Examples II-1 to II-3 were measured in accordance with ASTM-D2244 (color scale system 2) using a colorimeter "ZE-2000" manufactured by Nippon Denshoku Industries Co., Ltd. In addition, as an index of the hue after oxidation, the hues of the pellets obtained in each Example and Comparative Example after hot air drying at 120°C for 3 hours under air were also measured in the same manner.

[0150] (Example II-1: Preparation of pellets (EP1)) (1) Polymerization of ethylene-1-butene-5-ethylidene-2-norbornene copolymer Ethylene (feed rate: 150 L / h), 1-butene (feed rate: 35 L / h) and 5-ethylidene-2-norbornene (concentration in reactor: 5 g / L) were continuously fed into a 5 L continuous polymerization reactor equipped with an agitator, and the copolymerization reaction was carried out under the condition of 0.7 MPa while adjusting the water temperature in the jacket so that the internal temperature was 40°C. Cyclohexane solvent was continuously fed from the top of the polymerization reactor at a rate of 3 L / h, while the polymerization liquid was continuously extracted from the bottom of the polymerization reactor so that the volume of the polymerization liquid in the polymerization reactor was always 3 L. In addition, a cyclohexane solution of vanadium trichloride (V), a cyclohexane solution of diethylaluminum chloride and a cyclohexane solution of ethylaluminum dichloride were continuously fed as polymerization catalysts at metal atom concentrations of 0.5 mmol / L, 1.5 mmol / L and 1.5 mmol / L, respectively. In addition, hydrogen was used as a molecular weight regulator and was fed so that the hydrogen concentration in the gas phase in the polymerization reactor was 1 mol%.

[0151] Next, a small amount of methanol was added to the extracted polymerization solution to terminate the polymerization reaction, and the polymer was separated from the solvent by steam stripping, and then washed with water. It was then dried overnight under vacuum at 80°C. As a result, an ethylene-cyclic olefin copolymer (A) consisting of ethylene, 1-butene, and 5-ethylidene-2-norbornene was obtained at a rate of 90 g / hour.

[0152] (II-2) Preparation of pellets 10 parts by mass of the ethylene-cyclic olefin copolymer (A) obtained above, 0.4 parts by mass of cobalt stearate (II) as a transition metal catalyst (B), and 90 parts by mass of "Eval F171" (MFR = 1g / 10 min at 190 ° C. and 2160 g load) manufactured by Kuraray Co., Ltd. as an ethylene-vinyl alcohol copolymer (C) were mixed, melt-kneaded in a twin-screw kneading extruder (screw diameter 25 mmφ, L / D = 30, manufactured by Toyo Seiki Seisakusho Co., Ltd.) under conditions of a cylinder temperature of 230 ° C. and a screw rotation speed of 100 rpm, and then extruded from the die into a cooling water tank at 20 ° C. in the form of strands, and pelletized with a strand cutter to obtain pellets (EP1) of a resin composition. The color of the obtained pellets (EP1) was evaluated. The composition of the pellets (EP1) and the evaluation results of the color are shown in Table 5.

[0153] (Example II-2: Preparation of pellets (EP2)) An ethylene-1-butene-5-ethylidene-2-norbornene copolymer was obtained in the same manner as in Example II-1, except that the polymerization temperature was changed to 50°C instead of 40°C. Pellets (EP2) were produced in the same manner as in Example II-1, except that this ethylene-1-butene-5-ethylidene-2-norbornene copolymer was used. The composition of the obtained pellets (EP2) and the evaluation results of the color are shown in Table 5.

[0154] (Example II-3: Preparation of pellets (EP3)) In the polymerization, propylene was used instead of 1-butene, the feed rate of the propylene was set to 50 L / h, and the concentration of 5-ethylidene-2-norbornene in the reactor was changed to 2 g / L. An ethylene-propylene-5-ethylidene-2-norbornene copolymer was obtained in the same manner as in Example II-1. Pellets (EP3) were produced in the same manner as in Example II-1, except that this ethylene-propylene-5-ethylidene-2-norbornene copolymer was used. The composition of the obtained pellets (EP3) and the evaluation results of the color are shown in Table 5.

[0155] (Example II-4: Preparation of pellets (EP4)) In the polymerization, propylene was used instead of 1-butene, the feed rate of the propylene was set to 50 L / h, the concentration of 5-ethylidene-2-norbornene in the reactor was changed to 2 g / L, and the type of catalyst and the concentration in the reactor were changed to a cyclohexane solution of 0.1 mmol / L of the metallocene catalyst dichloro[rac-ethylenebis(4,5,6,7-tetrahydro-1-indenyl)]zirconium(IV) (manufactured by Aldrich Co.) and a cyclohexane solution of 3 mmol / L of methylaluminoxane prepared by the method described in the non-patent document (J.Polym.Sci.,PartA1988,26,3089.), to obtain an ethylene-propylene-5-ethylidene-2-norbornene copolymer in the same manner as in Example II-1. Pellets (EP4) were prepared in the same manner as in Example II-1, except that this ethylene-propylene-5-ethylidene-2-norbornene copolymer was used. The composition of the obtained pellets (EP4) and the evaluation results of the color are shown in Table 5.

[0156] (Example II-5: Preparation of pellets (EP5)) In the polymerization, propylene was used instead of 1-butene, the feed rate of the propylene was set to 50 L / h, the concentration of 5-ethylidene-2-norbornene in the reactor was changed to 2 g / L, and the type of catalyst and the concentration in the reactor were changed to a cyclohexane solution of 0.1 mmol / L of dichloro[rac-ethylenebis(4,5,6,7-tetrahydro-1-indenyl)]zirconium(IV) (manufactured by Aldrich Co.) and a cyclohexane solution of 0.1 mmol / L of triphenylmethylium tetrakis(pentafluorophenylborate) (manufactured by Tokyo Chemical Industry Co., Ltd.), respectively, to obtain an ethylene-propylene-5-ethylidene-2-norbornene copolymer in the same manner as in Example II-1. Pellets (EP5) were produced in the same manner as in Example II-1, except that this ethylene-propylene-5-ethylidene-2-norbornene copolymer was used. The composition of the obtained pellets (EP5) and the evaluation results of the color are shown in Table 5.

[0157] (Example II-6: Preparation of pellets (EP6)) In the polymerization, propylene was used instead of 1-butene, the feed rate of the propylene was set to 80 L / h, the concentration of 5-ethylidene-2-norbornene in the reactor was changed to 2 g / L, and the type of catalyst and the concentration in the reactor were changed to a cyclohexane solution of 0.1 mmol / L of the metallocene catalyst dichloro[rac-ethylenebis(4,5,6,7-tetrahydro-1-indenyl)]zirconium(IV) (manufactured by Aldrich Co.) and a cyclohexane solution of 3 mmol / L of methylaluminoxane prepared by the method described in the non-patent document (J.Polym.Sci.,PartA1988,26,3089.), to obtain an ethylene-propylene-5-ethylidene-2-norbornene copolymer in the same manner as in Example II-1. Pellets (EP6) were prepared in the same manner as in Example II-1, except that this ethylene-propylene-5-ethylidene-2-norbornene copolymer was used. The composition of the resulting pellets (EP6) and the evaluation results of the color are shown in Table 5.

[0158] (Example II-7: Preparation of pellets (EP7)) In a 5L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-propylene-5-ethylidene-2-norbornene copolymer pellets (NORDEL IP4820P manufactured by Dow Chemical Company) and 70 parts by mass of acetone were added, and the mixture was heated in an oil bath at 60°C under a nitrogen atmosphere and refluxed overnight to elute the acetone-soluble components contained in the ethylene-propylene-5-ethylidene-2-norbornene copolymer. The pellets were washed by filtration and washing with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Pellets (EP7) were prepared in the same manner as in Example II-1, except that such ethylene-propylene-5-ethylidene-2-norbornene copolymer pellets were used. The composition of the obtained pellets (EP7) is shown in Table 5.

[0159] (Example II-8: Preparation of pellets (EP8)) In a 5L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-propylene-5-ethylidene-2-norbornene copolymer pellets (NORDEL IP4770P manufactured by Dow Chemical Company) and 70 parts by mass of acetone were added, and the mixture was heated in an oil bath at 60°C under a nitrogen atmosphere and refluxed overnight to elute the acetone-soluble components contained in the ethylene-propylene-5-ethylidene-2-norbornene copolymer. The pellets were washed by filtration and washing with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Pellets (EP8) were prepared in the same manner as in Example II-1, except that such ethylene-propylene-5-ethylidene-2-norbornene copolymer pellets were used. The composition of the obtained pellets (EP8) is shown in Table 5.

[0160] When the resin composition was kneaded with a twin screw to produce the pellets (EP8), it was confirmed that a large amount of resin was generated on the die.

[0161] (Example II-9: Preparation of pellets (EP9)) A bale of ethylene-propylene-dicyclopentadiene copolymer (Esprene 301A manufactured by Sumitomo Chemical Co., Ltd.) was cut into 3 cm squares, and 5 parts by mass of this copolymer was dissolved in 100 parts by mass of cyclohexane at 80°C. The resulting solution was cooled to room temperature, and reprecipitated with a large amount of acetone while stirring at high speed, and the precipitated solid was vacuum dried at 80°C. The resulting solid was cut into 5 mm squares. Pellets (EP9) were produced in the same manner as in Example II-1, except that the cut solid was used. The composition of the resulting pellets (EP9) is shown in Table 5.

[0162] When the resin composition was kneaded with a twin screw to produce the pellets (EP9), it was confirmed that a large amount of resin was generated on the die.

[0163] (Example II-10: Preparation of pellets (EP10)) In a 5 L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-2-norbornene copolymer pellets (TOPAS E-140 manufactured by Polyplastics Co., Ltd.) and 70 parts by mass of acetone were added, and the mixture was heated in an oil bath at 60°C under a nitrogen atmosphere and refluxed overnight to elute the acetone-soluble components contained in the ethylene-2-norbornene copolymer. The pellets were washed by filtration and washing with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. A pellet (EP10) was prepared in the same manner as in Example II-1, except that such ethylene-2-norbornene copolymer pellets were used. The composition of the obtained pellets (EP10) is shown in Table 5.

[0164] (Example II-11: Preparation of pellets (EP11)) In a 5L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-1-butene-5-ethylidene-2-norbornene copolymer pellets (Mitsui EPT K-9720 manufactured by Mitsui Chemicals, Inc.) and 70 parts by mass of acetone were added, and the mixture was heated in an oil bath at 60°C under a nitrogen atmosphere and refluxed overnight to elute the acetone-soluble components contained in the ethylene-2-norbornene copolymer. The pellets were washed by filtration and washing with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Pellets (EP11) were prepared in the same manner as in Example II-1, except that such ethylene-1-butene-5-ethylidene-2-norbornene copolymer pellets were used. The composition of the obtained pellets (EP11) is shown in Table 5.

[0165] (Example II-12: Preparation of pellets (EP12)) Pellets (EP12) were produced in the same manner as in Example II-1, except that 0.4 parts by mass of manganese (II) stearate was used instead of cobalt (II) stearate. The composition of the resulting pellets (EP12) and the evaluation results of the color are shown in Table 5.

[0166] (Example II-13: Preparation of pellets (EP13)) In producing the pellets, 0.01 parts by mass of an antioxidant (Irganox1076 manufactured by BASF Japan Ltd.) was further added to the twin-screw kneading extruder, and the content of the ethylene-vinyl alcohol copolymer (C) was changed to 89.99 parts by mass. The pellets (EP13) were produced in the same manner as in Example II-1. The composition of the obtained pellets (EP13) and the evaluation results of the color are shown in Table 5.

[0167] (Example II-14: Preparation of pellets (EP14)) In a 5 L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-1-butene-5-ethylidene-2-norbornene copolymer pellets (Mitsui EPT K-9720, manufactured by Mitsui Chemicals, Inc.) and 70 parts by mass of acetone were added, and the mixture was refluxed overnight in a nitrogen atmosphere by heating in an oil bath at 60°C to elute the acetone-soluble components contained in the ethylene-2-norbornene copolymer. The pellets were washed by filtration and washing with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Using such ethylene-1-butene-5-ethylidene-2-norbornene copolymer pellets, a twin-screw kneading extruder was further fed with a plasticizer (HI-WAX800P, manufactured by Mitsui Chemicals, Inc.; low molecular weight HDPE, molecular weight 8000, density 0.970 kg / cm). 3 Pellets (EP14) were prepared in the same manner as in Example II-1, except that 2 parts by mass of ethylene-1-butene-5-ethylidene-2-norbornene pellets from which additives had been removed with acetone were added and the content of the pellets was changed to 8 parts by mass. The composition of the obtained pellets (EP14) is shown in Table 5.

[0168] (Example II-15: Preparation of pellets (EP15)) In a 5 L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-1-butene-5-ethylidene-2-norbornene copolymer pellets (Mitsui EPT K-9720, manufactured by Mitsui Chemicals, Inc.) and 70 parts by mass of acetone were added, and the mixture was refluxed overnight in a nitrogen atmosphere by heating in an oil bath at 60°C to elute the acetone-soluble components contained in the ethylene-2-norbornene copolymer. The pellets were washed by filtration and washing with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Using such ethylene-1-butene-5-ethylidene-2-norbornene copolymer pellets, a twin-screw kneading extruder was further fed with a plasticizer (HI-WAX800P, manufactured by Mitsui Chemicals, Inc.; low molecular weight HDPE, molecular weight 8000, density 0.970 kg / cm). 3 Pellets (EP15) were prepared in the same manner as in Example II-1, except that 4 parts by mass of ethylene-1-butene-5-ethylidene-2-norbornene was added, the content of pellets of ethylene-1-butene-5-ethylidene-2-norbornene from which additives had been removed with acetone was changed to 16 parts by mass, and the content of ethylene-vinyl alcohol copolymer (C) was changed to 80 parts by mass. The composition of the obtained pellets (EP15) is shown in Table 5.

[0169] (Example II-16: Preparation of pellets (EP16)) In a 5L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-propylene-5-ethylidene-2-norbornene copolymer pellets (NORDEL IP4770P manufactured by Dow Chemical Company) and 70 parts by mass of acetone were added, and the mixture was heated in an oil bath at 60°C under a nitrogen atmosphere and refluxed overnight to elute the acetone-soluble components contained in the ethylene-propylene-5-ethylidene-2-norbornene copolymer. The pellets were washed by filtration and with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Pellets (EP16) were prepared in the same manner as in Example II-1, except that pellets of such ethylene-propylene-5-ethylidene-2-norbornene copolymer were used, 3 parts by mass of ethylene-methyl methacrylate copolymer (Acryft WK-402, manufactured by Sumitomo Chemical Co., Ltd.; methyl methacrylate content 25 wt%, MFR = 20 g / 10 min) was further added to the twin-screw kneading extruder, and the content of the ethylene-propylene-5-ethylidene-2-norbornene pellets was changed to 7 parts by mass. The composition of the obtained pellets (EP16) is shown in Table 5.

[0170] (Example II-17: Preparation of pellets (EP17)) In a 5L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-propylene-5-ethylidene-2-norbornene copolymer pellets (NORDEL IP4770P manufactured by Dow Chemical Company) and 70 parts by mass of acetone were added, and the mixture was heated in an oil bath at 60°C under a nitrogen atmosphere and refluxed overnight to elute the acetone-soluble components contained in the ethylene-propylene-5-ethylidene-2-norbornene copolymer. The pellets were washed by filtration and with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Pellets (EP17) were produced in the same manner as in Example II-1, except that pellets of such ethylene-propylene-5-ethylidene-2-norbornene copolymer were used, 3 parts by mass of ethylene-methacrylic acid copolymer (Nucrel N1035 manufactured by Dow Mitsui Polychemicals Co., Ltd.; methacrylic acid content 10 wt%, MFR = 35 g / 10 min) was further added to the twin-screw kneading extruder, and the content of the ethylene-propylene-5-ethylidene-2-norbornene pellets was changed to 7 parts by mass. The composition of the obtained pellets (EP17) is shown in Table 5.

[0171] (Example II-18: Preparation of pellets (EP18)) In a 5L separable flask equipped with a stirring blade, 30 parts by mass of ethylene-propylene-5-ethylidene-2-norbornene copolymer pellets (NORDEL IP4770P manufactured by Dow Chemical Company) and 70 parts by mass of acetone were added, and the mixture was heated in an oil bath at 60°C under a nitrogen atmosphere and refluxed overnight to elute the acetone-soluble components contained in the ethylene-propylene-5-ethylidene-2-norbornene copolymer. The pellets were washed by filtration and with a large amount of acetone, and then vacuum dried at 60°C to remove the acetone contained in the pellets. Pellets (EP18) were prepared in the same manner as in Example II-1, except that pellets of such ethylene-propylene-5-ethylidene-2-norbornene copolymer were used, 0.45 parts by mass of calcium stearate (II) was added as an alkaline earth metal salt to the twin-screw kneader extruder, 3 parts by mass of ethylene-methacrylic acid copolymer (Nucrel N1035 manufactured by Mitsui Dow Polychemical Co., Ltd.; methacrylic acid content 10 wt%, MFR = 35 g / 10 min) was added, and the content of ethylene-propylene-5-ethylidene-2-norbornene pellets was changed to 7 parts by mass. The composition of the obtained pellets (EP18) is shown in Table 5.

[0172] In addition, when the resin composition was kneaded with a twin screw to produce the above pellets (EP16, 17, 18), it was confirmed that the occurrence of scum on the die, as confirmed in Example 8 (production of pellets (EP8)), was significantly reduced.

[0173] (Comparative Example II-1: Preparation of Pellet (CP1)) Pellets (CP1) were prepared in the same manner as in Example II-1, except that 10 parts by mass of polyoctenylene (a product of ring-opening metathesis polymerization of cyclooctene) (Veatenamer 8020 manufactured by EVONIK) was used instead of the ethylene-1-butene-5-ethylidene-2-norbornene copolymer, and the content of cobalt (II) stearate was changed to 0.2 parts by mass. The composition of the obtained pellets (CP1) and the evaluation results of the color are shown in Table 5.

[0174] (Comparative Example II-2: Preparation of Pellet (CP2)) Pellets (CP2) were prepared in the same manner as in Example II-1, except that the ethylene-1-butene-5-ethylidene-2-norbornene copolymer was not added and the content of the ethylene-vinyl alcohol copolymer (C) was changed to 100 parts by mass. The composition of the obtained pellets (CP2) is shown in Table 5.

[0175] (Comparative Example II-3: Preparation of Pellet (CP3)) Pellets (CP3) were prepared in the same manner as in Example II-1, except that 10 parts by mass of 1-hexene-modified L-LDPE (Harmolex NF325N manufactured by Japan Polyethylene Co., Ltd.) was used instead of the ethylene-1-butene-5-ethylidene-2-norbornene copolymer. The composition of the obtained pellets (CP3) is shown in Table 5.

[0176] [Table 5]

[0177] (Example II-19: Preparation of oxygen absorbing film (EF1)) The pellets (EP1) obtained in Example II-1 were put into a single layer extruder (screw diameter 20 mmφ, L / D=20, manufactured by Toyo Seiki Seisakusho Co., Ltd.), melt-kneaded at a cylinder temperature of 220°C and a screw rotation speed of 100 rpm, and cast from a die onto a cooling roll at 80°C to obtain an oxygen absorbing film (EF1) with a thickness of 20 μm. The oxygen absorbing film (EF1) was subjected to the above-mentioned oxygen absorption test, odor evaluation after oxygen absorption, and decomposition product evaluation. The obtained results are shown in Table 6.

[0178] (Examples II-20 to II-36: Preparation of oxygen absorbing films (EF2) to (EF18)) Oxygen absorbing films (EF2) to (EF18) were obtained in the same manner as in Example II-19, except that the pellets (EP2) to (EP18) prepared in Examples II-2 to II-18 were used instead of the pellets (EP1) prepared in Example II-1. The oxygen absorption test, odor evaluation after oxygen absorption, and decomposition product evaluation were performed on these oxygen absorbing films (EF2) to (EP18). The obtained results are shown in Table 6.

[0179] Many fisheyes were observed in the oxygen-absorbing films (EF8) and (EF9) obtained in Examples II-26 and II-27. In contrast, it was confirmed that the occurrence of fisheyes was significantly reduced in the oxygen-absorbing films (EF16 to EF18) obtained in Examples II-32 to II-34, as compared with, for example, the oxygen-absorbing film (EF8).

[0180] (Comparative Examples II-4 to II-6: Preparation of Oxygen Absorbing Films (CF1) to (CF3)) Oxygen absorbing films (CF1) to (CF3) were produced in the same manner as in Example II-17, except that the pellets (CP1) to (CP3) produced in Comparative Examples II-1 to II-3 were used instead of the pellets (EP1) produced in Example II-1. The oxygen absorbing films (CF1) to (CF3) were subjected to the above-mentioned oxygen absorption test, odor evaluation after oxygen absorption, and decomposition product evaluation. The obtained results are shown in Table 6.

[0181] [Table 6]

[0182] As shown in Table 6, the oxygen absorbing films (EF1) to (EF18) produced in Examples II-19 to II-36 showed higher oxygen absorption than the films (CF2) and (CF3) obtained in Comparative Examples II-5 and II-6, which did not contain the ethylene-cyclic olefin copolymer (A). The film (CF3) of Comparative Example II-4 had a high oxygen absorption, but the average odor evaluation score was significantly higher than that of the oxygen absorbing films (EF1) to (EF18) produced in Examples II-19 to II-36. Furthermore, it can be seen that the generation of valeraldehyde, as measured in Comparative Examples II-4 and II-6, was hardly observed in the oxygen absorbing films (EF1) to (EF18) produced in Examples II-19 to II-36.

[0183] (Example II-37: Preparation of thermoformed cup (EC1)) Polypropylene (Novatec EA7AD manufactured by Japan Polypropylene Corporation) was fed into the first extruder as the base resin, maleic anhydride modified polypropylene (Admer QF-500 manufactured by Mitsui Chemicals, Inc.) was fed into the second extruder as the adhesive resin, and the pellets (EP1) obtained in Example 1 were fed into the third extruder as the oxygen absorbing resin. Using a three-kind, five-layer multilayer extruder, a three-kind, five-layer multilayer sheet was produced under conditions of an extrusion temperature of 180 to 230°C and a die temperature of 230°C, with a layer structure of polypropylene (320μm) / adhesive layer (45μm) / oxygen absorbing resin layer (80μm) / adhesive layer (40μm) / polypropylene (320μm).

[0184] This multilayer sheet was molded using a vacuum / compressed air molding machine (manufactured by Asano Laboratory Co., Ltd.) under the conditions of a sheet surface temperature of 190°C, a pressure of 0.3 MPa, and a drawing ratio of 0.5 to produce a thermoformed cup (EC1). The oxygen barrier properties of this thermoformed cup (EC1) during the retort treatment were evaluated. The results are shown in Table 7.

[0185] (Examples II-38 to II-54: Preparation of Thermoformed Cups (EC2) to (EC18)) Thermoformed cups (EC2) to (EC18) were produced in the same manner as in Example II-37, except that the pellets (EP2) to (EP18) produced in Examples II-2 to II-18 were used instead of the pellets (EP1) produced in Example II-1. The oxygen barrier properties of these thermoformed cups (EC2) to (EC18) during the retort treatment were evaluated. The results are shown in Table 7.

[0186] (Comparative Examples II-7 to II-9: Preparation of Thermoformed Cups (CC1) to (CC3)) Thermoformed cups (CC1) to (CC3) were produced in the same manner as in Example II-33, except that pellets (CP1) to (CP3) produced in Comparative Examples II-1 to II-3 were used instead of pellets (EP1) produced in Example II-1. The oxygen barrier properties of these thermoformed cups (CC1) to (CC3) during the retort treatment were evaluated. The results are shown in Table 7.

[0187] [Table 7]

[0188] As shown in Table 7, the thermoformed cups (EC1) to (EC18) produced in Examples II-37 to II-54 were able to keep the dissolved oxygen concentration low after retort treatment compared to the thermoformed cups (CC2) and (CC3) of Comparative Examples II-8 and II-9, which used pellets (CP2) and (CP3) that did not contain ethylene-cyclic olefin copolymer (A), and it can be seen that they had excellent oxygen barrier properties when subjected to retort treatment. [Industrial Applicability]

[0189] The resin composition of the present invention is useful for packaging various products in technical fields such as the food and beverage field, the pet food field, the oil and fat industry field, and the pharmaceutical field.

Claims

1. An ethylene unit represented by the following formula (I) and a substituent R 1 A resin composition comprising an ethylene-cyclic olefin copolymer (A) containing a repeating unit with a norbornene unit having the formula: and a transition metal catalyst (B), 【Chemistry 1】 In the formula, R 1 represents an ethylene group or an ethylene group substituted with an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and l and n represent the ethylene unit and the substituent R 1 The ratio of l to n (l / n) is 4 or more and 2000 or less, The ethylene-cyclic olefin copolymer (A) is a copolymer having a branched chain composed of at least one alkyl group selected from the group consisting of an n-butyl group, an n-pentyl group, and an n-hexyl group, and 13 The resin composition has a total number of the alkyl groups constituting the branched chains per 1,000 carbon atoms of 0.001 to 5, as determined by C NMR.

2. The ethylene-cyclic olefin copolymer (A) is an ethylene unit represented by the following formula (II) and a substituent R 2 and an ethylene unit having a substituent R 1 and a norbornene unit having the formula 【Chemistry 2】 (In the formula, R 1 represents an ethylene group or an ethylene group substituted with an aliphatic hydrocarbon group having 1 to 3 carbon atoms; R 2 represents an aliphatic hydrocarbon group having 1 to 8 carbon atoms; l, m and n represent the ethylene unit, the substituent R 2 and the substituent R 1 represents the content ratio of norbornene units having the formula The resin composition according to claim 1 , wherein l, m and n satisfy the relationship of the following formula (III). 0.0005≦n / (l+m+n)≦0.2 (III)

3. R in formula (II) 2 is at least one group selected from the group consisting of a linear, branched or cyclic alkyl group having 1 to 8 carbon atoms; a linear, branched or cyclic alkenyl group having 2 to 8 carbon atoms; and a linear, branched or cyclic alkynyl group having 2 to 8 carbon atoms.

4. R in the formula (I) 1 is an ethylene group substituted with at least one aliphatic hydrocarbon group selected from the group consisting of a linear, branched or cyclic alkyl group having 1 to 3 carbon atoms; a linear, branched or cyclic alkenyl group having 2 to 3 carbon atoms; an alkynyl group having 2 to 3 carbon atoms; and a linear or branched alkylidene group having 2 to 3 carbon atoms. The resin composition according to claim 1 ,

5. R in the formula (I) 1 The resin composition according to claim 1 , wherein is an ethylideneethylene group.

6. The resin composition according to claim 2 or 3, wherein R 1 in formula (II) is an ethylene group substituted with at least one aliphatic hydrocarbon group selected from the group consisting of linear, branched or cyclic alkyl groups having 1 to 3 carbon atoms; linear, branched or cyclic alkenyl groups having 2 to 3 carbon atoms; alkynyl groups having 2 to 3 carbon atoms; and linear or branched alkylidene groups having 2 to 3 carbon atoms.

7. The resin composition according to claim 2, wherein R 1 in formula (II) is an ethylideneethylene group.

8. The resin composition according to any one of claims 1 to 7, wherein the main chain of the ethylene-cyclic olefin copolymer (A) is composed of only single bonds.

9. The resin composition according to any one of claims 1 to 8, which has an oxygen absorption rate of 0.1 to 300 mL / g for 7 days under conditions of 60°C and 10% RH.

10. The resin composition according to any one of claims 1 to 9, wherein the content of the transition metal catalyst (B) is 20 to 10,000 ppm in terms of metal atoms.

11. The content X (ppm) of the transition metal catalyst (B) in terms of metal atoms and the number of the substituents R in all the monomer units constituting the ethylene-cyclic olefin copolymer (A) are 1 The resin composition according to any one of claims 1 to 10, wherein the content ratio Y (mol%) of the norbornene unit having the formula (IV) is satisfied. 11≦X / Y≦10000 (IV)

12. The content X (ppm) of the transition metal catalyst (B) in terms of metal atoms and the number of the substituents R in all the monomer units constituting the ethylene-cyclic olefin copolymer (A) are 1 and the content ratio Y (mol %) of norbornene units having the substituent R 2 The resin composition according to claim 2, 3, 6 or 7, wherein the content ratio Z (mol%) of the ethylene unit having the formula (V) below is satisfied. 0.1≦X / (Y+Z)≦150 (V)

13. The resin composition according to any one of claims 1 to 12, wherein the content of the ethylene-cyclic olefin copolymer (A) is 25.0 to 99.9 mass% based on the total amount of the resin composition.

14. The resin composition according to any one of claims 1 to 12, further comprising an ethylene-vinyl alcohol copolymer (C).

15. The resin composition according to claim 14, wherein the content of the ethylene-cyclic olefin copolymer (A) is 0.5 to 50 mass% based on the total amount of the resin composition.

16. The resin composition according to claim 14, wherein the content of the ethylene-vinyl alcohol copolymer (C) is 50 to 99.5 mass% based on the total amount of the resin composition.

17. The resin composition according to any one of claims 14 to 16, further comprising an alkaline earth metal salt, the content of which is 1 to 1000 ppm in terms of metal element.

18. The resin composition according to any one of claims 1 to 17, further comprising an aluminum compound (D), the aluminum compound being contained in an amount of 0.1 to 10,000 ppm in terms of aluminum metal atom.

19. The resin composition according to any one of claims 1 to 18, further comprising an acetic acid adsorbing material (E).

20. The resin composition according to claim 19, wherein the acetic acid adsorbing material (E) contains zeolite, and the content of the zeolite is 0.1 to 20 mass% based on the total amount of the resin composition.

21. The resin composition according to claim 20, wherein the zeolite has an average pore diameter of 0.3 to 1 nm.

22. The resin composition according to any one of claims 1 to 21, further comprising an antioxidant (F), and the content of the antioxidant is 0.001 to 1 mass% based on the total amount of the resin composition.

23. The ethylene-cyclic olefin copolymer (A) has an MFR of 2 g / 10 min or less at 190° C. under a load of 2160 g, The resin composition according to any one of claims 1 to 22, further comprising a viscosity modifier having an MFR of 10 g / 10 min or more at 190 ° C. under a load of 2160 g, and the content of the viscosity modifier is 1 to 30 mass % based on the total amount of the resin composition.

24. A multilayer structure having at least one oxygen absorbing layer comprising the resin composition according to any one of claims 1 to 23.

25. The multilayer structure according to claim 24, comprising at least one gas barrier resin layer.

26. A packaging material comprising the multi-layer structure of claim 25.

27. 27. The packaging material according to claim 26, which comprises: A packaged product, wherein the oxygen absorbing layer in the packaging material is disposed between the gas barrier resin layer in the packaging material and the contents.

28. 28. The packaged product of claim 27, wherein the contents are a food product.

Citation Information

Patent Citations

  • Dryblending of neutralized sulfonated elastomer powder

    JP1979088951A

  • Polypropylene resin composition

    JP1981086944A

  • oxygen scavenger

    JP1993247258A

  • Oxygen scavenging compositions, articles and methods with improved physical properties

    JP1996502306A

  • Oxygen-absorbing resin composition

    JP2005320513A